Molding resin sheet and molded product using the same

By setting a high-hardness resin layer and hard coating layer on the resin sheet, adjusting the glass transition temperature of the resin layer and the delay characteristics of the adhesive layer, the problem of uneven color combination of the resin front panel and the touch sensor under the polarized sunglasses is solved. It also improves the hardness and anti-glare properties of the resin board, simplifies the curved surface forming process, and improves productivity.

CN114174041BActive Publication Date: 2024-12-17MITSUBISHI GAS CHEM CO INC +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202080055078.7
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2019-08-09
Filing Date
2020-08-04
Publication Date
2024-12-17
Estimated Expiration
2040-08-04

AI Technical Summary

Technical Problem

The combination of existing resin front panel and touch sensor is prone to uneven color or coloring problems when wearing polarized sunglasses, and it is difficult to achieve uniform anti-glare treatment when bending, which affects the visual recognition and productivity of the display panel.

Method used

A resin sheet for molding containing polycarbonate resin as a base material is used, and a high-hard resin layer, a hard coat layer or a hard coat anti-glare layer is provided on the surface, and the glass transition temperature relationship of the resin layer and the delay of the adhesive layer are adjusted. Characteristics ensure that the resin sheet is not prone to abnormal appearance during thermoforming, and improves its hardness and anti-glare properties.

Benefits of technology

It is realized that resin molded products that suppress uneven color or coloring while wearing polarized sunglasses are suppressed, which improves the hardness and anti-glare properties of the resin plate, simplifies the molding process of curved resin plates, and improves productivity.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0003493696970000041
    Figure BDA0003493696970000041
  • Figure BDA0003493696970000042
    Figure BDA0003493696970000042
  • Figure BDA0003493696970000051
    Figure BDA0003493696970000051
Patent Text Reader

Abstract

The present invention can provide a molding resin sheet, which has a high-hardness resin layer containing a high-hardness resin on at least one surface of a substrate layer containing a polycarbonate resin (a1), and a hard coating layer or a hard coating anti-glare layer is laminated on at least one side surface of the high-hardness resin layer, the glass transition temperatures of the polycarbonate resin (a1) and the high-hardness resin satisfy the following relationship: -10°C ≤ (glass transition temperature of the high-hardness resin) - (glass transition temperature of the polycarbonate resin (a1)) ≤ 40°C, the in-plane retardation of the resin sheet when measured at a wavelength of 543nm is greater than 4000nm, and a resin film (X) having an in-plane retardation of less than 50nm when measured at a wavelength of 543nm is adhered to one side surface of the resin sheet using an adhesive layer containing an adhesive.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a molding resin sheet and a molded product using the same. Background Art

[0002] The components of the display surface of the instrument cover and other automobile interior decorations, home appliances, OA equipment, personal computers, small mobile devices, etc. use glass plates, transparent resin plates, etc., and the frame parts that hold them use resin molded bodies. On the other hand, the components of the touch panel type display surface used for mobile phone terminals, etc. use components formed by bonding a transparent sheet, especially a glass plate, to a frame part formed by injection molding resin using double-sided adhesive tape. As a touch panel type display surface, the thinner the better from the aspect of response speed, and from the aspect of strength, a certain degree of thickness is required, so a material with a high elastic modulus is selected. In addition, scratch resistance, fingerprint wiping resistance, etc. are also required.

[0003] The resin molded body used for the above-mentioned purposes can be manufactured by molding a resin sheet, and various studies have been conducted to impart properties corresponding to the purpose. For example, the resin sheet is modified with a hard coating, a decorative sheet, etc., or a resin sheet is formed by laminating resin layers having different compositions, or the composition of the resin used is studied.

[0004] As the decorative sheet, for example, an acrylic resin may be used, a decorative sheet having a hard coat layer, or a decorative sheet obtained by laminating a film after providing a design such as printing, etc., may be used.

[0005] For example, Patent Document 1 discloses a decorative sheet having a transparent acrylic resin sheet layer, a pattern printing ink layer, an ABS resin sheet layer, and an ABS resin substrate layer laminated in order from the surface side. Patent Document 2 discloses a multilayer film having a layer containing methacrylic resin and acrylic rubber particles laminated on the surface of a polycarbonate resin layer, and discloses a decorative sheet having a thermoplastic resin sheet laminated on the decorative surface after decorating one surface of the multilayer film. Also disclosed is a decorative molded product manufactured by injection molding a thermoplastic resin on the decorative surface.

[0006] Patent Document 3 discloses a resin molded product obtained by molding using a sheet having a thermosetting or ultraviolet curing hard coating layer provided on a resin substrate.

[0007] In addition, Patent Document 4 discloses a decorative hard coating film having a layer formed by using a hard coating paint of a specific composition on one surface of a base film, and also discloses that a printed layer can be provided on the base film. The decorative film can be thermoformed. The decorative film described in Patent Document 4 is integrated with a molding resin to form a decorative molded product.

[0008] Patent Document 5 discloses a laminated sheet including a base layer mainly composed of a polycarbonate resin composition and a cover layer mainly composed of an acrylic resin on one surface of the base layer.

[0009] In addition, the components of the display surface may also be provided with an anti-glare layer to disperse the reflection of external light and make the display easier to see. The anti-glare treatment can be implemented by giving a fine structure or shape to the surface.

[0010] When the display surface is curved, in the case of using a glass plate as a front panel component, it is necessary to bend the glass plate before applying an anti-glare treatment. This is because the anti-glare layer cannot withstand the bending temperature of the glass and will disappear. However, it is difficult to uniformly anti-glare the curved surface. On the other hand, when using a resin plate, the flat plate can be pre-treated with an anti-glare treatment before bending. The bending temperature of the resin plate is significantly lower than the bending temperature of the glass, and the anti-glare layer will not disappear, so there is an advantage that the curved surface does not need to be anti-glare treated.

[0011] The display surfaces of car navigation systems, smartphones, etc. are often given a touch panel function. When the display surface is curved, it is very difficult to bond the touch sensor to the curved resin front panel. Therefore, before the resin plate is given a curved shape, the touch sensor is pre-bonded in a flat state, and then the resin plate and the touch sensor are shaped at the same time. This method does not require bonding the touch sensor to the curved front panel, and as a manufacturing process, the productivity is very high.

[0012] Prior art literature

[0013] Patent Literature

[0014] Patent Document 1: Japanese Patent Application Publication No. 2001-334609

[0015] Patent Document 2: Japanese Patent Application Publication No. 2009-234184

[0016] Patent Document 3: Japanese Patent Publication No. 4-40183

[0017] Patent Document 4: Japanese Patent Application Publication No. 2010-284910

[0018] Patent Document 5: Japanese Patent Application Publication No. 2009-196153 Summary of the invention

[0019] Technical problem to be solved by the invention

[0020] The inventors of the present invention have studied the combination of a resin front panel and a touch sensor, and as a result, a high-latency resin front panel and a low-latency resin film touch sensor are suitable. This is because when a combination of latencies other than the above is used, when viewing a car navigation system or a smartphone while wearing polarized sunglasses, color unevenness or coloration occurs, and visibility deteriorates.

[0021] Even in the case of a combination of a high-latency resin front panel and a low-latency resin film touch sensor, as long as the lag axis of the resin front panel and the resin film touch sensor are bonded in a parallel or perpendicular relationship, color unevenness or coloration will not occur, but there is a high possibility of axis deviation during shaping.

[0022] Among them, the inventors of the present invention found that the delay of the high-delay resin front panel can be greater than 3500nm, and can be 4000nm, and the delay of the low-delay resin film touch sensor can be less than 100nm, and can be less than 50nm.

[0023] When bending a resin plate, a metal mold, a wooden mold, a resin mold, or the like is often used to press a heated resin plate to perform heat bending.

[0024] The pursuit of a resin sheet or film capable of producing a resin molded body having properties more suitable for a specific application is an endless task.

[0025] The object of the present invention is to provide a molding resin sheet having high hardness, which is less likely to have abnormal appearance during molding and can suppress color unevenness or coloring even when wearing polarized sunglasses, and a resin molded product using the same.

[0026] Technical solutions for solving technical problems

[0027] The inventors of the present invention have carefully studied a resin sheet for molding comprising a polycarbonate resin as a substrate and a resin sheet having a hard coating layer on the surface, and a resin film touch sensor bonded to the resin sheet. As a result, it was found that a high-hardness resin layer was provided between the polycarbonate resin layer and the hard coating layer, and further, as the polycarbonate resin and the high-hardness resin, resins whose respective glass transition temperatures satisfy a prescribed relationship were selected, thereby providing a resin sheet with high hardness and which is not prone to appearance abnormalities such as cracks and flow marks during molding. In addition, by selecting the delay of the resin sheet and the delay of the bonded resin film touch sensor, even after the molding resin sheet with the film sensor is thermally formed, color unevenness or coloring can be suppressed when wearing polarized sunglasses. That is, for example, the present invention is as described below.

[0028] <1> A molding resin sheet, comprising a high-hardness resin layer containing a high-hardness resin on at least one surface of a substrate layer containing a polycarbonate resin (a1), and a hard coating layer or a hard coating antiglare layer laminated on at least one surface of the high-hardness resin layer,

[0029] The glass transition temperatures of the polycarbonate resin (a1) and the high hardness resin satisfy the following relationship:

[0030] -10°C ≤ (glass transition temperature of high hardness resin) - (glass transition temperature of polycarbonate resin (a1)) ≤ 40°C,

[0031] The in-plane retardation of the resin sheet when measured at a wavelength of 543 nm is 4000 nm or more,

[0032] A resin film (X) having an in-plane retardation of 50 nm or less when measured at a wavelength of 543 nm is bonded to one surface of the resin sheet via an adhesive layer containing an adhesive.

[0033] <2> The molding resin sheet according to <1> above, wherein the polycarbonate resin (a1) is an aromatic polycarbonate resin.

[0034] <3> The molding resin sheet according to <2>, wherein the aromatic polycarbonate resin contains a structural unit represented by the following general formula (4a).

[0035]

[0036] <4> The molding resin sheet according to any one of <1> to <3>, wherein the content of the polycarbonate resin (a1) is 75 to 100% by mass based on the total mass of the substrate layer.

[0037] <5> The molding resin sheet according to any one of <1> to <4>, wherein the high hardness resin is selected from the following resins (B1) to (B6):

[0038] Resin (B1): a copolymer comprising a (meth)acrylate structural unit (a) represented by the following general formula (1) and an aliphatic vinyl structural unit (b) represented by the following general formula (2), or an alloy of the copolymer and resin (B2);

[0039]

[0040] (In formula (1), R1 is a hydrogen atom or a methyl group; R2 is an alkyl group having 1 to 18 carbon atoms.)

[0041]

[0042] (In formula (2), R3 is a hydrogen atom or a methyl group; R4 is a cyclohexyl group which may be substituted by a hydrocarbon group having 1 to 4 carbon atoms.)

[0043] Resin (B2): a copolymer (D) comprising 6 to 77% by mass of a (meth)acrylate structural unit, 15 to 71% by mass of a styrene structural unit and 8 to 23% by mass of an unsaturated dicarboxylic acid structural unit, an alloy of the copolymer (D) or an alloy of the copolymer (D) and another high hardness resin, or an alloy of the copolymer (D) and an acrylic resin;

[0044] Resin (B3): a copolymer comprising a structural unit (c) represented by the following general formula (6) and optionally a structural unit (d) represented by the following general formula (7);

[0045]

[0046] Resin (B4): a copolymer (G) comprising 5 to 20% by mass of a styrene structural unit, 60 to 90% by mass of a (meth)acrylate structural unit and 5 to 20% by mass of an N-substituted maleimide structural unit, or an alloy of the copolymer (G) and the above-mentioned resin (B2);

[0047] Resin (B5): A resin comprising a structural unit (e) represented by the following general formula (8).

[0048]

[0049] Resin (B6): An alloy of a copolymer containing 50 to 95% by mass of a styrene structural unit and 5 to 50% by mass of an unsaturated dicarboxylic acid unit, and an acrylic resin.

[0050] <6> The molding resin sheet according to any one of <1> to <5>, wherein the content of the high hardness resin is 70 to 100% by mass based on the total mass of the high hardness resin layer.

[0051] <7> The molding resin sheet according to any one of <1> to <6>, wherein the total thickness of the base layer and the high-hardness resin layer is 0.5 mm to 3.5 mm.

[0052] <8> The molding resin sheet according to any one of <1> to <7>, wherein the thickness of the base layer accounts for 75% to 99% of the total thickness of the base layer and the high-hardness resin layer.

[0053] <9> The molding resin sheet according to any one of <1> to <8>, wherein the molding resin sheet has a haze of 2 to 30%.

[0054] <10> The molding resin sheet according to any one of <1> to <9>, wherein the pencil hardness of the surface of the hard coat layer of the molding resin sheet is 2H or more.

[0055] <11> The molding resin sheet according to any one of <1> to <10>, wherein the resin film (X) of the molding resin sheet comprises a polycarbonate film containing a polycarbonate resin (a1).

[0056] <12> The molding resin sheet according to any one of <1> to <10>, wherein the resin film (X) of the molding resin sheet includes a film touch sensor in which a sensor electrode is applied to a polycarbonate film.

[0057] <13> The molding resin sheet according to any one of <1> to <12>, wherein the adhesive layer of the molding resin sheet is an optical adhesive sheet.

[0058] <14> A resin molded product obtained by molding using the molding resin sheet according to any one of <1> to <13>.

[0059] Effects of the Invention

[0060] The present invention can provide a resin sheet for molding that has high hardness, is not prone to abnormal appearance during molding, and can suppress color unevenness or coloring even when wearing polarized sunglasses, and a resin molded product using the same. In the present invention, a high-hardness resin layer is provided on a base layer containing a polycarbonate resin, and a hard coating layer or a hard coating antiglare layer is further provided on the outside, so that a resin plate that is not easily scratched, has antiglare properties, has good visibility, and is easy to bend by heat can be provided. DETAILED DESCRIPTION

[0061] Hereinafter, the present invention will be described in detail with reference to production examples and embodiments, but the present invention is not limited to the production examples and embodiments, and can be carried out by changing to any method within the scope not greatly departing from the content of the present invention.

[0062] The molding resin sheet of the present invention (hereinafter, also referred to as "resin sheet") comprises a substrate layer containing a polycarbonate resin (a1), a high hardness resin layer containing a high hardness resin, and a hard coating layer or a hard coating anti-glare layer, wherein the high hardness resin layer is located between the substrate layer and the hard coating layer or the hard coating anti-glare layer. Other layers may be present between the substrate layer and the high hardness resin layer, and between the high hardness resin layer and the hard coating layer or the hard coating anti-glare layer, respectively. As other layers, adhesive layers, primer layers, etc. may be listed, but are not limited to these. Other layers may also be absent. As one embodiment, a resin sheet comprising a substrate layer containing a polycarbonate resin (a1), a high hardness resin layer laminated on at least one surface of the substrate layer, and a hard coating layer or a hard coating anti-glare layer laminated on the high hardness resin layer is provided.

[0063] As long as the high hardness resin layer and hard coating or hard coating anti-glare layer are arranged on at least one side of the base material layer, there is no particular restriction on the formation of the other side. In addition, the high hardness resin layer can also be arranged on the both sides of the base material layer. In this case, hard coating or hard coating anti-glare layer can be arranged on one or two high hardness resin layers. When the high hardness resin layer is arranged on the both sides of the base material layer, in order to obtain the few stable resin sheets of warping, it is hoped that 2 high hardness resin layers use the same high hardness resin.

[0064] As described above, the molding resin sheet of the present invention is provided with a high hardness resin layer between the substrate layer and the hard coating layer or the hard coating anti-glare layer, and the glass transition temperature of the polycarbonate resin (a1) in the substrate layer and the high hardness resin in the high hardness resin layer satisfies the prescribed relationship, thereby being able to obtain a resin sheet with high hardness and not prone to abnormal appearance such as cracks and flow marks during molding. In particular, it is not easy to have abnormal appearance during thermoforming, and such a resin sheet can widely set the conditions (temperature, heating time, etc.) during thermoforming, so it can be called a resin sheet suitable for thermoforming. In addition, by pre-bonding a resin film touch sensor before molding a resin sheet suitable for thermoforming, the difficult process of bonding the touch sensor to the front panel with a curved surface after molding can be omitted. Therefore, the productivity of the front panel of a display screen with a curved surface can be improved.

[0065] As the present invention, the resin sheet having a hard coat layer or a hard coating anti-glare layer with high hardness on the surface, particularly the resin sheet using polycarbonate resin as the base material, has excellent impact resistance, high safety, and light weight compared with the common glass plate. In addition, compared with the common glass plate, it is easy to bend and will not crack due to a small amount of bending. Consider that this is because the hard coat layer or the hard coating anti-glare layer in the resin sheet has a certain degree of flexibility.

[0066] By providing a high-hardness resin layer between the substrate layer and the hard-coated anti-glare layer, the hardness of the resin sheet can be further improved. When the hard-coated anti-glare layer is directly provided on the polycarbonate resin layer, problems such as low elastic modulus and easy buckling may occur, but by providing a high-hardness resin layer, such problems can also be solved.

[0067] In the present invention, the glass transition temperatures of the polycarbonate resin (a1) in the base material layer and the high hardness resin in the high hardness resin layer satisfy the following relationship.

[0068] -10℃≤(glass transition temperature of high hardness resin)-(glass transition temperature of polycarbonate resin (a1))≤40℃

[0069] Conventionally, when different types of resin layers are laminated and a hard coating layer is provided thereon, the glass transition temperature (Tg) or melt viscosity of the resins contained in each layer is different, and there is a problem that it is difficult to perform thermoforming without causing undesirable problems such as cracks. However, by using the present invention, such a problem can be solved by using a polycarbonate resin (a1) and a high hardness resin that satisfy the above relationship.

[0070] When a multilayer resin sheet is thermoformed into a desired shape, the molding is usually performed in accordance with the molding temperature of the resin that contains the most in the layer. For example, in the case of a resin sheet using a polycarbonate resin as the substrate layer, the polycarbonate resin with good impact resistance is usually contained the most, so thermoforming is performed using a molding temperature that matches the polycarbonate resin. Since the resin sheet of the present invention uses a polycarbonate resin (a1) that satisfies the above relationship and a high-hardness resin, it is not easy to have problems with abnormal appearance even when thermoforming is performed at a molding temperature suitable for polycarbonate resin. Therefore, compared with existing resin sheets, the resin sheet of the present invention can be called a resin sheet suitable for thermoforming.

[0071] The glass transition temperatures of the polycarbonate resin (a1) and the high hardness resin are preferably -5°C ≤ (glass transition temperature of the high hardness resin) - (glass transition temperature of the polycarbonate resin (a1)) ≤ 30°C, and more preferably 0°C ≤ (glass transition temperature of the high hardness resin) - (glass transition temperature of the polycarbonate resin (a1)) ≤ 30°C. When the Tg of the high hardness resin is extremely lower than the Tg of the polycarbonate resin (a1), the high hardness resin becomes a rubbery state or a molten state during thermoforming and becomes easy to move. In this case, the hard coat anti-glare layer, which has a highly cross-linked structure and remains hard even when heated, cannot move along with the movement of the high hardness resin that becomes easy to move, and cracks are easily generated. On the other hand, when the Tg of the high hardness resin is too high compared to the Tg of the polycarbonate resin (a1), the difference in viscosity between the high hardness resin and the polycarbonate resin becomes large, and when they are laminated, the interface may become rough and flow marks may occur.

[0072] The resin sheet of the present invention can be suitably used for the production of molded products having curved shapes that require hardness. For example, components having a flat portion and a continuous curved portion can be smoothly produced, and thus products having novel designs and functions can be provided.

[0073] In the case of manufacturing a molded product having the above-mentioned shape in the existing resin sheet, cracks and the like are often generated during hot forming such as hot pressing, vacuum forming, pressure forming, and TOM forming. Therefore, in order to suppress the generation of cracks during hot forming, it is necessary to reduce the hardness of the hard coating layer, etc. However, when the hardness of the hard coating layer is reduced, although the hot forming property is improved, the hard coating layer becomes soft, thus generating new problems such as easy scratching and reduced chemical resistance.

[0074] In contrast, the present invention can provide a resin sheet that can be thermoformed without reducing the hardness of the hard coating layer because the generation of cracks is suppressed as described above. The resin sheet of the present invention is not easily scratched and has high chemical resistance because a hard hard coating anti-glare layer can be provided on the surface. Utilizing such characteristics, the resin sheet of the present invention can be used for components of display surfaces of computers, mobile phones, etc., components for automobile exterior and interior decoration, mobile phone terminals, computers, tablet PCs, car navigation, etc., housings or front panels with curved surfaces, etc.

[0075] Hereinafter, each component of the resin sheet of the present invention will be described.

[0076] 1. Base material layer

[0077] The substrate layer is a resin layer mainly containing a polycarbonate resin (a1). The polycarbonate resin (a1) contained in the substrate layer may be one kind or two or more kinds. The content of the polycarbonate resin (a1) in the substrate layer is preferably 75 to 100% by mass, more preferably 90 to 100% by mass, and particularly preferably 100% by mass relative to the total mass of the substrate layer. By increasing the content of the polycarbonate resin, the impact resistance is improved.

[0078] The polycarbonate resin (a1) is not particularly limited as long as it contains a carbonate bond, i.e., -[O-R-OCO]- unit in the main chain of the molecule (wherein R may contain an aliphatic group, an aromatic group, or both an aliphatic group and an aromatic group, and may be a linear structure or a branched structure), but is preferably an aromatic polycarbonate resin, and particularly preferably a polycarbonate resin containing a structural unit of the following formula (4a). By using such a polycarbonate resin, a resin sheet having better impact resistance can be obtained.

[0079]

[0080] Specifically, as the polycarbonate resin (a1), an aromatic polycarbonate resin (for example, Iupilon S-2000, Iupilon S-1000, Iupilon E-2000; manufactured by Mitsubishi Engineering-Plastics Corporation) or the like can be used.

[0081] In recent years, polycarbonate resins obtained by adding a monohydric alcohol represented by the following general formula (4) as a terminal terminator have also been used for the purpose of controlling the glass transition temperature of polycarbonate resins. In the present invention, polycarbonate resins to which such a terminal terminator has been added can also be used.

[0082]

[0083] (In the formula, R1 represents an alkyl group having 8 to 36 carbon atoms or an alkenyl group having 8 to 36 carbon atoms; R2 to R5 each independently represent a hydrogen atom, a halogen, or an alkyl group having 1 to 20 carbon atoms or an aryl group having 6 to 12 carbon atoms which may have a substituent; wherein the substituent is a halogen, an alkyl group having 1 to 20 carbon atoms or an aryl group having 6 to 12 carbon atoms.)

[0084] In the present specification, "alkyl" and "alkenyl" may be linear or branched, and may have a substituent.

[0085] More preferably, the monohydric alcohol represented by the general formula (4) is represented by the following general formula (5).

[0086]

[0087] (In the formula, R1 represents an alkyl group having 8 to 36 carbon atoms or an alkenyl group having 8 to 36 carbon atoms.)

[0088] The number of carbon atoms of R1 in the general formula (4) or (5) is more preferably within a specific numerical range. Specifically, the upper limit of the number of carbon atoms of R1 is preferably 36, more preferably 22, and particularly preferably 18. In addition, the lower limit of the number of carbon atoms of R1 is preferably 8, and more preferably 12.

[0089] Among the monohydric alcohols represented by the general formula (4) or (5), it is particularly preferred to use either or both of hexadecyl p-hydroxybenzoate and 2-hexyldecyl p-hydroxybenzoate as the terminal terminator.

[0090] For example, in the general formula (5), when a monohydric alcohol in which R1 is an alkyl group having 16 carbon atoms is used as a terminal terminator, a polycarbonate resin having excellent glass transition temperature, melt fluidity, moldability, sag resistance, etc. can be obtained. In addition, when manufacturing a polycarbonate resin, the solvent solubility of the monohydric alcohol is also excellent, so it is particularly preferred.

[0091] On the other hand, when the number of carbon atoms of R1 in the general formula (4) or (5) is too large, the solubility of the monohydric alcohol (terminator) in an organic solvent tends to decrease, and productivity may decrease when producing a polycarbonate resin.

[0092] As an example, if the carbon number of R1 is 36 or less, the productivity is high and the economic efficiency is good when manufacturing polycarbonate resin. If the carbon number of R1 is 22 or less, the organic solvent solubility of the monohydric alcohol is particularly excellent, and the productivity can be made very high and the economic efficiency is also improved when manufacturing polycarbonate resin. As polycarbonate resins obtained using such monohydric alcohols, for example, Iupizeta T-1380 (manufactured by Mitsubishi Gas Chemical) and the like can be cited.

[0093] When the number of carbon atoms of R1 in the general formula (4) or (5) is too small, the glass transition temperature of the polycarbonate resin may not be sufficiently low, and the thermoformability may be reduced.

[0094] In the present invention, the weight average molecular weight of the polycarbonate resin (a1) can affect the impact resistance and molding conditions of the resin sheet. That is, when the weight average molecular weight is too small, the impact resistance of the resin sheet may decrease. When the weight average molecular weight is too high, an excess heat source is sometimes required when forming a substrate layer containing the polycarbonate resin (a1). In addition, since a high temperature is required due to the selected molding method, the polycarbonate resin (a1) is exposed to high temperatures, which sometimes has an adverse effect on its thermal stability. The weight average molecular weight of the polycarbonate resin (a1) is preferably 15,000 to 75,000, and more preferably 20,000 to 70,000. It is further preferably 20,000 to 65,000. Among them, the weight average molecular weight in this specification is the weight average molecular weight converted to standard polystyrene measured by gel permeation chromatography (GPC).

[0095] If a person skilled in the art considers the glass transition temperature (Tg) of the high hardness resin used, a polycarbonate resin (a1) having a Tg satisfying the above relationship can be appropriately selected and used from known polycarbonate resins. The Tg of the polycarbonate resin (a1) is preferably 90 to 190°C, more preferably 100 to 170°C, and particularly preferably 110 to 150°C. In this specification, the glass transition temperature is a temperature calculated by the midpoint method using a differential scanning calorimeter and measuring 10 mg of a sample at a heating rate of 10°C / min.

[0096] The substrate layer may contain other resins in addition to the polycarbonate resin (a1). Examples of such resins include polyester resins, etc. The polyester resin preferably mainly contains terephthalic acid as a dicarboxylic acid component, but may contain dicarboxylic acid components other than terephthalic acid.

[0097] For example, a polyester resin (so-called "PETG") obtained by polycondensation of a diol component containing 20 to 40 mol% of 1,4-cyclohexanedimethanol (total 100 mol%) relative to 80 to 60 mol% of ethylene glycol as a main component is preferred. The resin of the substrate layer is preferably only the polycarbonate resin (a1), and when other resins are included, the amount thereof is preferably 0 to 25% by mass, more preferably 0 to 10% by mass, relative to the total mass of the substrate layer.

[0098] The substrate layer may also contain additives, etc. As additives, additives commonly used in resin sheets may be used, and examples of such additives include antioxidants, anti-coloring agents, antistatic agents, mold release agents, lubricants, dyes, pigments, plasticizers, flame retardants, resin modifiers, compatibilizers, reinforcing materials such as organic fillers and inorganic fillers, etc. The method of mixing the additives with the resin is not particularly limited, and a method of mixing the entire amount, a method of dry-mixing the masterbatch, a method of dry-mixing the entire amount, etc. may be used. The amount of the additive is preferably 0 to 10% by mass, more preferably 0 to 7% by mass, and particularly preferably 0 to 5% by mass relative to the total mass of the substrate layer.

[0099] The thickness of the substrate layer is preferably 0.3 to 10 mm, more preferably 0.3 to 5 mm, and particularly preferably 0.3 to 3.5 mm.

[0100] 2. High hardness resin layer

[0101] The high hardness resin layer is a resin layer mainly containing a high hardness resin. In this specification, the high hardness resin is a resin having a higher hardness than the polycarbonate resin forming the substrate, and refers to a resin with a pencil hardness of HB or above. The pencil hardness of the high hardness resin is preferably HB to 3H, more preferably H to 3H, and particularly preferably 2H to 3H. The high hardness resin contained in the high hardness resin layer may be one type or two or more types. If a person skilled in the art can consider the glass transition temperature (Tg) of the polycarbonate resin used, a high hardness resin having a Tg that satisfies the relationship of "-10°C ≤ (glass transition temperature of high hardness resin) - (glass transition temperature of polycarbonate resin (a1)) ≤ 40°C" can be appropriately selected from the known high hardness resins and used. The high hardness resin is preferably selected from at least one of the resins (B1) to (B6) shown below.

[0102] <Resin (B1)>

[0103] The resin (B1) is a copolymer comprising a (meth)acrylate structural unit (a) represented by the following general formula (1) and an aliphatic vinyl structural unit (b) represented by the following general formula (2), or an alloy of the copolymer and the resin (B2) described below.

[0104]

[0105] (In the formula, R1 is a hydrogen atom or a methyl group; R2 is an alkyl group having 1 to 18 carbon atoms.)

[0106]

[0107] (In the formula, R3 is a hydrogen atom or a methyl group; R4 is a cyclohexyl group which may be substituted by a hydrocarbon group having 1 to 4 carbon atoms.)

[0108] In the present specification, the "hydrocarbon group" may be linear, branched, or cyclic, and may have a substituent.

[0109] In the (meth)acrylate structural unit (a) represented by the general formula (1), R2 is an alkyl group having 1 to 18 carbon atoms, preferably an alkyl group having 1 to 10 carbon atoms, and more preferably an alkyl group having 1 to 6 carbon atoms. Specific examples thereof include methyl, ethyl, butyl, lauryl, stearyl, cyclohexyl, and isobornyl.

[0110] Among the (meth)acrylate structural units (a), preferred are (meth)acrylate structural units in which R2 is a methyl group or an ethyl group, and more preferred are methyl methacrylate structural units in which R1 is a methyl group and R2 is a methyl group.

[0111] In the aliphatic vinyl structural unit (b) represented by the general formula (2), R3 is a hydrogen atom or a methyl group, more preferably a hydrogen atom. R4 is a cyclohexyl group or a cyclohexyl group substituted with a hydrocarbon group having 1 to 4 carbon atoms, preferably an unsubstituted cyclohexyl group.

[0112] Therefore, among the aliphatic vinyl structural units (b), more preferred are those in which R3 is a hydrogen atom and R4 is a cyclohexyl group.

[0113] The resin (B1) may contain one or more (meth)acrylate structural units (a), and may contain one or more aliphatic vinyl structural units (b).

[0114] The total content of the (meth)acrylate structural unit (a) and the aliphatic vinyl structural unit (b) is preferably 90 to 100 mol %, more preferably 95 to 100 mol %, particularly preferably 98 to 100 mol % based on all structural units of the resin (B1).

[0115] That is, the resin (B1) may contain structural units other than the (meth)acrylate structural unit (a) and the aliphatic vinyl structural unit (b), and the amount thereof is preferably 10 mol% or less, more preferably 5 mol% or less, and particularly preferably 2 mol% or less relative to the total structural units of the resin (B1).

[0116] Examples of structural units other than the (meth)acrylate structural unit (a) and the aliphatic vinyl structural unit (b) include structural units derived from an aromatic vinyl monomer having an unhydrogenated aromatic double bond, which is produced in the process of producing the resin (B1) by polymerizing a (meth)acrylate monomer and an aromatic vinyl monomer and then hydrogenating the aromatic double bond derived from the aromatic vinyl monomer.

[0117] In addition, the content of the (meth)acrylate structural unit (a) represented by the general formula (1) is preferably 65 to 80 mol%, more preferably 70 to 80 mol%, relative to the total structural units in the resin (B1). When the ratio of the (meth)acrylate structural unit (a) is 65 mol% or more relative to the total structural units in the resin (B1), a resin layer having excellent adhesion to the substrate layer and surface hardness can be obtained. In addition, when it is 80 mol% or less, the resin sheet is less likely to warp due to water absorption.

[0118] In addition, the content of the aliphatic vinyl structural unit (b) represented by the general formula (2) is preferably 20 to 35 mol%, more preferably 20 to 30 mol%, relative to the total structural units in the resin (B1). When the content of the aliphatic vinyl structural unit (b) is 20 mol% or more, warping under high temperature and high humidity can be prevented, and when it is 35 mol% or less, peeling at the interface with the substrate layer can be prevented.

[0119] In this specification, the "copolymer" may be any structure of a random, block or alternating copolymer.

[0120] The method for producing the resin (B1) is not particularly limited, and it is preferably obtained by polymerizing at least one (meth)acrylate monomer and at least one aromatic vinyl monomer, and then hydrogenating the aromatic double bonds derived from the aromatic vinyl monomer. (Meth)acrylic acid refers to methacrylic acid and / or acrylic acid.

[0121] Specific examples of the aromatic vinyl monomer used in this case include styrene, α-methylstyrene, p-hydroxystyrene, alkoxystyrene, chlorostyrene, and derivatives thereof. Among these, styrene is preferred.

[0122] The (meth)acrylic acid ester monomer and the aromatic vinyl monomer can be polymerized by a known method, for example, the polymerization can be carried out by a bulk polymerization method, a solution polymerization method, or the like.

[0123] The bulk polymerization method can be carried out by a method in which a monomer composition containing the above-mentioned monomers and a polymerization initiator is continuously supplied to a complete mixing tank and continuously polymerized at 100 to 180° C. The above-mentioned monomer composition may contain a chain transfer agent as required.

[0124] The polymerization initiator is not particularly limited, and examples thereof include organic peroxides such as tert-amyl peroxy-2-ethylhexanoate, tert-butyl peroxy-2-ethylhexanoate, benzoyl peroxide, 1,1-di(tert-hexylperoxy)-3,3,5-trimethylcyclohexane, 1,1-di(tert-hexylperoxy)cyclohexane, 1,1-di(tert-butylperoxy)cyclohexane, tert-hexylpropoxyisopropylmonocarbonate, tert-amylperoxy-n-octanoate, tert-butylperoxyisopropylmonocarbonate, and di-tert-butylperoxide, and azo compounds such as 2,2'-azobisisobutyronitrile, 2,2'-azobis(2-methylbutyronitrile), and 2,2'-azobis(2,4-dimethylvaleronitrile). These may be used alone or in combination of two or more.

[0125] A chain transfer agent is used as necessary, and an example thereof is α-methylstyrene dimer.

[0126] Examples of the solvent used in the solution polymerization method include hydrocarbon solvents such as toluene, xylene, cyclohexane, and methylcyclohexane, ester solvents such as ethyl acetate and methyl isobutyrate, ketone solvents such as acetone and methyl ethyl ketone, ether solvents such as tetrahydrofuran and dioxane, and alcohol solvents such as methanol and isopropanol.

[0127] The solvent used in the hydrogenation reaction after polymerization of the (meth)acrylate monomer and the aromatic vinyl monomer may be the same as or different from the above-mentioned polymerization solvent, and examples thereof include hydrocarbon solvents such as cyclohexane and methylcyclohexane, ester solvents such as ethyl acetate and methyl isobutyrate, ketone solvents such as acetone and methyl ethyl ketone, ether solvents such as tetrahydrofuran and dioxane, and alcohol solvents such as methanol and isopropanol.

[0128] The resin (B1) used in the present invention can be obtained by polymerizing the (meth)acrylic acid ester monomer and the aromatic vinyl monomer and then hydrogenating the aromatic double bonds derived from the aromatic vinyl monomer.

[0129] The method of hydrogenation is not particularly limited, and a known method can be used. For example, it can be carried out in a batch or continuous flow manner at a hydrogen pressure of 3 to 30 MPa and a reaction temperature of 60 to 250° C. By setting the temperature to 60° C. or higher, the reaction time will not be too long, and by setting the temperature to 250° C. or lower, the molecular chain cleavage or hydrogenation of the ester site will rarely occur.

[0130] Examples of the catalyst used for the hydrogenation reaction include solid catalysts obtained by supporting metals such as nickel, palladium, platinum, cobalt, ruthenium, and rhodium, or oxides, salts, or coordination compounds of these metals on porous carriers such as carbon, alumina, silica, silica-alumina, and diatomaceous earth.

[0131] Resin (B1) preferably has 70% or more of the aromatic double bonds derived from the aromatic vinyl monomer hydrogenated. That is, the unhydrogenated rate of the aromatic double bonds contained in the structural unit derived from the aromatic vinyl monomer is preferably less than 30%. By having an unhydrogenated rate of less than 30%, a resin with excellent transparency can be obtained. The unhydrogenated rate is more preferably less than 10%, and further preferably less than 5%.

[0132] The weight average molecular weight of the resin (B1) is not particularly limited, but is preferably 50,000 to 400,000, more preferably 70,000 to 300,000, from the viewpoint of strength and moldability.

[0133] The glass transition temperature of the resin (B1) is preferably in the range of 110 to 140°C, more preferably 110 to 135°C, and particularly preferably 110 to 130°C. When the glass transition temperature is 110°C or higher, the resin sheet provided by the present invention rarely deforms or breaks in a hot environment or a hot and humid environment. On the other hand, when the glass transition temperature is 140°C or lower, excellent processability is achieved when molding is performed by continuous heat forming using a mirror roll or a shaping roll, or by intermittent heat forming using a mirror die or a shaping die.

[0134] Specific examples of the resin (B1) include Optimas 7500 and 6000 (manufactured by Mitsubishi Gas Chemical Co., Ltd.).

[0135] When using resin (B1) as a high-hardness resin, it is preferred to use Iupizeta T-1380 (manufactured by Mitsubishi Gas Chemical) as the polycarbonate resin (a1). The following method is particularly preferred: as resin (B1), a copolymer containing 75 mol% of a structural unit represented by general formula (1) (R1 and R2 are both methyl groups; methyl methacrylate) and 25 mol% of a structural unit represented by general formula (2) (R3 is a hydrogen atom, and R4 is a cyclohexyl group) is used; as polycarbonate resin (a1), a polycarbonate resin containing a structural unit represented by general formula (4a) is used; as a terminal terminator, a monohydric alcohol represented by general formula (5) (the number of carbon atoms of R1 is 8 to 22) is used.

[0136] <Resin (B2)>

[0137] Resin (B2) is a copolymer (D) containing 6 to 77% by mass of (meth)acrylate structural units, 15 to 71% by mass of styrene structural units, and 8 to 23% by mass of unsaturated dicarboxylic acid structural units, or a resin as an alloy of copolymers (D), as well as a resin as an alloy of a high-hardness resin other than the copolymer (D) and the resin (B2), or as a resin as an alloy of a copolymer (D) and an acrylic resin. As high-hardness resins other than the resin (B2), methyl methacrylate-styrene copolymers, acrylonitrile-butadiene-styrene copolymers, etc. can be listed. In addition, as acrylic resins, polymethyl methacrylate, copolymers of methyl methacrylate and methyl acrylate or ethyl acrylate, etc. can be listed. In addition, commercially available products can also be used, and as specific examples, Acrypet of Mitsubishi Chemical Corporation, Sumipex of Sumitomo Chemical Co., Ltd., Parapet of Kuraray Co., Ltd., ALTUGLAS of Arkema, etc. can be exemplified. In the case of an alloy, in order to avoid a decrease in the Tg of a high-hardness resin, an alloy of resins having higher Tg is preferred.

[0138] Examples of the (meth)acrylate monomers constituting the (meth)acrylate structural unit include acrylic acid, methyl acrylate, ethyl acrylate, n-butyl acrylate, 2-ethylhexyl acrylate, methacrylic acid, methyl methacrylate, ethyl methacrylate, n-butyl methacrylate, 2-ethylhexyl methacrylate, and the like, with methyl methacrylate being particularly preferred. Two or more of these (meth)acrylate monomers may be used in combination.

[0139] The content of the (meth)acrylate structural unit is 6 to 77% by mass, preferably 20 to 70% by mass, based on the total mass of the resin (B2).

[0140] As the styrene structural unit, there is no particular limitation, and any known styrene monomer can be used. From the viewpoint of ease of acquisition, styrene, α-methylstyrene, o-methylstyrene, m-methylstyrene, p-methylstyrene, tert-butylstyrene, etc. are preferred. Among these, styrene is particularly preferred from the viewpoint of compatibility. These styrene monomers can also be used in combination of two or more.

[0141] The content of the styrene structural unit is 15 to 71% by mass, preferably 20 to 66% by mass, based on the total mass of the resin (B2).

[0142] As the unsaturated dicarboxylic acid anhydride monomer constituting the unsaturated dicarboxylic acid structural unit, for example, anhydrides of maleic acid, itaconic acid, citraconic acid, aconitic acid, etc. can be cited, and maleic anhydride is preferred from the viewpoint of compatibility with styrene monomers. These unsaturated dicarboxylic acid anhydride monomers can also be used in combination of two or more.

[0143] The content of the unsaturated dicarboxylic acid structural unit is 8 to 23% by mass, preferably 10 to 23% by mass, based on the total mass of the resin (B2).

[0144] The total content of the (meth)acrylate structural unit, styrene structural unit and unsaturated dicarboxylic acid structural unit is preferably 90 to 100 mol %, more preferably 95 to 100 mol %, particularly preferably 98 to 100 mol % based on all structural units of the resin (B2).

[0145] That is, the resin (B2) may also contain structural units other than the above-mentioned (meth)acrylate structural units, styrene structural units and unsaturated dicarboxylic acid structural units, and the amount thereof is preferably 10 mol% or less, more preferably 5 mol% or less, and particularly preferably 2 mol% or less relative to the total structural units of the resin (B2).

[0146] As other structural units, N-phenylmaleimide etc. are mentioned, for example.

[0147] The method for producing the resin (B2) is not particularly limited, and examples thereof include bulk polymerization and solution polymerization.

[0148] Specific examples of the resin (B2) include RESISFY R100, R200, and R310 (manufactured by Denka), DELPET980N (manufactured by Asahi Kasei Chemicals), and hw55 (manufactured by Daicel-Evonik).

[0149] The weight average molecular weight of the resin (B2) is not particularly limited, but is preferably 50,000 to 300,000, and more preferably 80,000 to 200,000.

[0150] The glass transition temperature of the resin (B2) is preferably 90 to 150°C, more preferably 100 to 150°C, particularly preferably 115 to 150°C.

[0151] When resin (B2) is used as a high hardness resin, it is preferred to use a polycarbonate resin containing a structural unit of the general formula (4a) as the polycarbonate resin (a1). In addition, it is particularly preferred to use a monohydric alcohol represented by the general formula (5) (the number of carbon atoms of R1 is 8 to 22) as a terminal terminator. Examples of such polycarbonate resins include Iupizeta T-1380 (manufactured by Mitsubishi Gas Chemical Co., Ltd.) and Iupilon E-2000 (manufactured by Mitsubishi Engineering-Plastics Co., Ltd.). It is preferred to use a copolymer (R100, R200 or R310; manufactured by Denka) composed of 6 to 26% by mass of methyl methacrylate structural units, 55 to 21% by mass of styrene structural units, and 15 to 23% by mass of maleic anhydride structural units as the resin (B2) and to use Iupizeta T-1380 as the polycarbonate resin (a1). Particularly preferred is an embodiment in which a copolymer composed of 6 mass % of methyl methacrylate structural units, 71 mass % of styrene structural units and 23 mass % of maleic anhydride structural units (R310; manufactured by Denka) is used as the resin (B2) and Iupizeta T-1380 is used as the polycarbonate resin (a1).

[0152] <Resin (B3)>

[0153] Resin (B3) is a copolymer comprising a structural unit (c) represented by the following general formula (6) and optionally a structural unit (d) represented by the following general formula (7). Resin (B3) may or may not contain structural unit (d), but preferably contains structural unit (d).

[0154]

[0155] The proportion of the structural unit (c) in all the structural units of the resin (B3) is preferably 50 to 100 mol%, more preferably 60 to 100 mol%, and particularly preferably 70 to 100 mol%. The proportion of the structural unit (d) in all the structural units of the resin (B3) is preferably 0 to 50 mol%, more preferably 0 to 40 mol%, and particularly preferably 0 to 30 mol%.

[0156] The total content of the structural unit (c) and the structural unit (d) is preferably 90 to 100 mol %, more preferably 95 to 100 mol %, particularly preferably 98 to 100 mol % based on the resin (B3).

[0157] The resin (B3) may contain structural units other than the structural units (c) and (d). When other structural units are contained, their amount is preferably 10 mol% or less, more preferably 5 mol% or less, and particularly preferably 2 mol% or less relative to all the structural units of the resin (B3).

[0158] As other structural units, for example, there can be mentioned structural units represented by the following general formula (4a).

[0159]

[0160] The method for producing the resin (B3) is not particularly limited, and the resin (B3) can be produced by the same method as the method for producing the polycarbonate resin (a1) described above, except that bisphenol C is used as a monomer.

[0161] Specific examples of the resin (B3) include Iupilon KH3410UR, KH3520UR, and KS3410UR (manufactured by Mitsubishi Engineering-Plastics Corporation).

[0162] The weight average molecular weight of the resin (B3) is preferably 15,000 to 75,000, more preferably 20,000 to 70,000, particularly preferably 25,000 to 65,000.

[0163] The glass transition temperature of the resin (B3) is preferably 105 to 150°C, more preferably 110 to 140°C, particularly preferably 110 to 135°C.

[0164] When using resin (B3) as a high hardness resin, it is preferred to use a polycarbonate resin containing a structural unit of the general formula (4a) as the polycarbonate resin (a1). In addition, it is particularly preferred to use a monohydric alcohol represented by the general formula (5) (the number of carbon atoms of R1 is 8 to 22) as a terminal terminator. As such a polycarbonate resin, Iupizeta T-1380 (manufactured by Mitsubishi Gas Chemical) can be cited. It is particularly preferred to use Iupilon KS3410UR (manufactured by Mitsubishi Engineering-Plastics Co., Ltd.) as resin (B3) and Iupizeta T-1380 (manufactured by Mitsubishi Gas Chemical) as polycarbonate resin (a1).

[0165] When resin (B3) is used as the high hardness resin, the other resin contained in the high hardness resin layer is preferably a resin containing structural unit (d) without structural unit (c), and more preferably a resin consisting only of structural unit (d). Specifically, aromatic polycarbonate resins (e.g., Iupilon S-2000, Iupilon S-1000, Iupilon E-2000; manufactured by Mitsubishi Engineering-Plastics Co., Ltd.) and the like can be used. When other resins are included, the resin (B3) is preferably included in a ratio of 45% by mass or more, more preferably 55% by mass or more relative to the total resins contained in the high hardness resin layer.

[0166] <Resin (B4)>

[0167] The resin (B4) is a copolymer (G) comprising 5 to 20% by mass of a styrene structural unit, 60 to 90% by mass of a (meth)acrylate structural unit, and 5 to 20% by mass of an N-substituted maleimide structural unit, or an alloy of the copolymer (G) and the above-mentioned resin (B2). In the case of an alloy, an alloy of resins with higher Tg is preferred to avoid a decrease in the Tg of the high-hardness resin layer.

[0168] As the styrene structural unit, there is no particular limitation, and any known styrene-based monomer can be used. From the viewpoint of ease of acquisition, styrene, α-methylstyrene, o-methylstyrene, m-methylstyrene, p-methylstyrene, tert-butylstyrene, etc. are preferred. Among these, styrene is particularly preferred from the viewpoint of compatibility. The copolymer (G) may also contain two or more of these styrene structural units. The content of the styrene structural unit is 5 to 20% by mass, preferably 5 to 15% by mass, and more preferably 5 to 10% by mass, relative to the total mass of the resin (B4).

[0169] As the (meth)acrylate structural unit, for example, structural units derived from acrylic acid, methyl acrylate, ethyl acrylate, n-butyl acrylate, 2-ethylhexyl acrylate, methacrylic acid, methyl methacrylate, ethyl methacrylate, n-butyl methacrylate, 2-ethylhexyl methacrylate, etc. can be cited, and structural units derived from methyl methacrylate are particularly preferred. In addition, copolymer (G) may also contain two or more of these (meth)acrylate structural units. The content of the (meth)acrylate structural unit is 60 to 90% by mass, preferably 70 to 90% by mass, and more preferably 80 to 90% by mass relative to the total mass of resin (B4).

[0170] As the N-substituted maleimide structural unit in the resin (B4), there can be cited structural units derived from N-phenylmaleimide, N-chlorophenylmaleimide, N-methylphenylmaleimide, N-naphthylmaleimide, N-hydroxyphenylmaleimide, N-methoxyphenylmaleimide, N-carboxyphenylmaleimide, N-nitrophenylmaleimide, N-tribromophenylmaleimide, etc. N-arylmaleimide and the like. From the viewpoint of compatibility with acrylic resin, structural units derived from N-phenylmaleimide are preferred. The copolymer (G) may also contain two or more of these N-substituted maleimide structural units. The content of the N-substituted maleimide structural unit is 5 to 20% by mass, preferably 5 to 15% by mass, and more preferably 5 to 10% by mass relative to the total mass of the resin (B4).

[0171] The total content of the styrene structural unit, the (meth)acrylate structural unit and the N-substituted maleimide structural unit is preferably 90 to 100 mol %, more preferably 95 to 100 mol %, particularly preferably 98 to 100 mol % based on the resin (B4).

[0172] The resin (B4) may contain structural units other than the above-mentioned structural units. When other structural units are contained, the amount thereof is preferably 10 mol% or less, more preferably 5 mol% or less, and particularly preferably 2 mol% or less, relative to all structural units of the resin (B4).

[0173] Examples of other structural units include structural units derived from the following general formula (1) and structural units derived from the following general formula (2).

[0174]

[0175] (In the formula, R1 is a hydrogen atom or a methyl group; R2 is an alkyl group having 1 to 18 carbon atoms.)

[0176]

[0177] (In the formula, R3 is a hydrogen atom or a methyl group; R4 is a cyclohexyl group which may be substituted by a hydrocarbon group having 1 to 4 carbon atoms.)

[0178] The method for producing the resin (B4) is not particularly limited, and the resin (B4) can be produced by solution polymerization, bulk polymerization, or the like.

[0179] Specific examples of the resin (B4) include DELPET PM120N (manufactured by Asahi Kasei Chemicals Corporation).

[0180] The weight average molecular weight of the resin (B4) is preferably 50,000 to 250,000, more preferably 100,000 to 200,000.

[0181] The glass transition temperature of the resin (B4) is preferably 110 to 150°C, more preferably 115 to 140°C, particularly preferably 115 to 135°C.

[0182] When using resin (B4) as a high hardness resin, it is preferred to use a polycarbonate resin containing a structural unit of the general formula (4a) as the polycarbonate resin (a1). In addition, it is particularly preferred to use a monohydric alcohol represented by the general formula (5) (the number of carbon atoms of R1 is 8 to 22) as a terminal terminator. As such a polycarbonate resin, Iupizeta T-1380 (manufactured by Mitsubishi Gas Chemical) can be cited. It is particularly preferred to use DELPET PM-120N containing 7% by mass of styrene structural units, 86% by mass of (meth)acrylate structural units and 7% by mass of N-substituted maleimide structural units as resin (B4) and to use Iupizeta T-1380 as the polycarbonate resin (a1).

[0183] <Resin (B5)>

[0184] The resin (B5) is a resin containing a structural unit (e) represented by the following general formula (8).

[0185]

[0186] The ratio of the structural unit (e) in all the structural units of the resin (B5) is preferably 80 to 100 mol %, more preferably 90 to 100 mol %, particularly preferably 95 to 100 mol %.

[0187] The resin (B5) may contain structural units other than the structural unit (e), and is preferably a polycarbonate resin composed of the structural unit (e). When other structural units are contained, the amount thereof is preferably 20 mol% or less, more preferably 10 mol% or less, and particularly preferably 5 mol% or less relative to the total structural units of the resin (B5).

[0188] Examples of other structural units include structural units represented by the following general formula (6) and structural units represented by the following general formula (7).

[0189]

[0190] The method for producing the resin (B5) is not particularly limited, and the resin (B5) can be produced by the same method as the method for producing the polycarbonate resin (a1) described above, except that bisphenol AP is used as a monomer.

[0191] Specific examples of the resin (B5) include Iupizeta FPC0220 (manufactured by Mitsubishi Gas Chemical Co., Ltd.).

[0192] The weight average molecular weight of the resin (B5) is preferably 10,000 to 1,000,000, more preferably 15,000 to 50,000.

[0193] The glass transition temperature of the resin (B5) is preferably 120 to 200°C, more preferably 130 to 190°C, particularly preferably 140 to 190°C.

[0194] When using resin (B5) as a high hardness resin, it is preferred to use a polycarbonate resin containing a structural unit of general formula (4a) as the polycarbonate resin (a1). As such a polycarbonate resin, Iupilon E-2000 (manufactured by Mitsubishi Engineering-Plastics Corporation) can be cited. It is particularly preferred to use Iupizeta FPC0220 (manufactured by Mitsubishi Gas Chemical) as resin (B5) and Iupilon E-2000 (manufactured by Mitsubishi Engineering-Plastics Corporation) as the polycarbonate resin (a1).

[0195] When resin (B5) is used as the high hardness resin, as other resins contained in the high hardness resin layer, it is preferred that the resin does not contain the structural unit (e) but contains the structural unit (d) described in resin (B3), and more preferably a resin consisting only of the structural unit (d). Specifically, aromatic polycarbonate resins (e.g., Iupilon S-2000, Iupilon S-1000, Iupilon E-2000; manufactured by Mitsubishi Engineering-Plastics Co., Ltd.) etc. can be used. When other resins are included, the resin (B5) is preferably included in a ratio of 45% by mass or more, more preferably 55% by mass or more relative to the total resins contained in the high hardness resin layer.

[0196] <Resin (B6)>

[0197] The resin (B6) is a copolymer (H) containing 50 to 95% by mass of a styrene structural unit and 5 to 50% by mass of an unsaturated dicarboxylic acid structural unit, or an alloy of the copolymer (H) and the above-mentioned resin (B1), or an alloy of the copolymer (H) and an acrylic resin. In the case of an alloy, an alloy of resins with higher Tg is preferred to avoid a decrease in the Tg of the high-hardness resin layer.

[0198] As the styrene structural unit, a styrene monomer described in resin (B4) can be used. Copolymer (H) may also contain two or more of these styrene structural units. The content of the styrene structural unit is 50 to 95% by mass, preferably 60 to 90% by mass, and more preferably 65 to 87% by mass relative to the total mass of the copolymer (H).

[0199] As the unsaturated dicarboxylic acid anhydride monomer constituting the unsaturated dicarboxylic acid structural unit, for example, anhydrides of maleic acid, itaconic acid, citraconic acid, aconitic acid, etc. can be cited, and maleic anhydride is preferred from the viewpoint of compatibility with styrene monomers. These unsaturated dicarboxylic acid anhydride monomers can be used in combination of two or more.

[0200] The content of the unsaturated dicarboxylic acid structural unit is 5 to 50% by mass, preferably 10 to 40% by mass, and more preferably 13 to 35% by mass, based on the total mass of the copolymer (H).

[0201] The copolymer (H) may contain structural units other than the above-mentioned structural units. When other structural units are contained, their amount is preferably 10 mol% or less, more preferably 5 mol% or less, and particularly preferably 2 mol% or less, based on all structural units of the resin (H).

[0202] Examples of other structural units include structural units derived from the following general formula (1) and structural units derived from the following general formula (2).

[0203]

[0204] (In the formula, R1 is a hydrogen atom or a methyl group; R2 is an alkyl group having 1 to 18 carbon atoms.)

[0205]

[0206] (In the formula, R3 is a hydrogen atom or a methyl group; R4 is a cyclohexyl group which may be substituted by a hydrocarbon group having 1 to 4 carbon atoms.)

[0207] The method for producing the copolymer (H) is not particularly limited, and the copolymer (H) can be produced by solution polymerization, bulk polymerization, or the like.

[0208] Specific examples of the copolymer (H) include XIBOND140 and XIBOND160 (manufactured by Polyskop).

[0209] The weight average molecular weight of the copolymer (H) is preferably 50,000 to 250,000, more preferably 100,000 to 200,000.

[0210] The content of the copolymer (H) containing styrene structural units and unsaturated dicarboxylic acid structural units is preferably 10 to 90 mass %, more preferably 20 to 85 mass %, particularly preferably 30 to 80 mass % based on the resin (B6).

[0211] The glass transition temperature of the resin (B6) is preferably 110 to 150°C, more preferably 115 to 140°C, particularly preferably 115 to 137°C.

[0212] When using resin (B6) as a high hardness resin, it is preferred to use a polycarbonate resin containing a structural unit of the general formula (4a) as the polycarbonate resin (a1). In addition, it is particularly preferred to use a monohydric alcohol (R1 has 8 to 22 carbon atoms) represented by the general formula (5) as a terminal terminator. As such a polycarbonate resin, Iupizeta T-1380 (manufactured by Mitsubishi Gas Chemical) can be cited. It is particularly preferred to use an alloy of XIBOND160 containing 78% by mass of styrene structural units and 22% by mass of maleic anhydride structural units and an acrylic resin as the resin (B6) and to use Iupizeta T-1380 as the polycarbonate resin (a1).

[0213] The high hardness resin contained in the high hardness resin layer may be one kind or two or more kinds. When two or more kinds are selected from the resins (B1) to (B6), they may be selected from the same or different kinds, and may contain high hardness resins other than the resins (B1) to (B6). The content of the high hardness resin in the high hardness resin layer is preferably 70 to 100% by mass, more preferably 80 to 100% by mass, and particularly preferably 100% by mass.

[0214] In addition to the high hardness resin described above, the high hardness resin layer may also contain other resins. As such resins, methyl methacrylate-styrene copolymers, polymethyl methacrylate, polystyrene, polycarbonate, cycloolefin (co)polymer resins, acrylonitrile-styrene copolymers, acrylonitrile-butadiene-styrene copolymers, various elastomers, etc. can be cited. The resin in the high hardness resin layer is preferably only the high hardness resin. When other resins are contained, the amount thereof is preferably less than 35% by mass, more preferably less than 25% by mass, and particularly preferably less than 10% by mass relative to the high hardness resin layer.

[0215] The high-hardness resin layer may further contain additives, etc. As the additives, the same additives as those described in the above-mentioned "1. Base material layer" can be used, and the amounts thereof are also the same.

[0216] The thickness of the high-hardness resin layer affects the surface hardness and impact resistance of the molding resin sheet. That is, when the high-hardness resin layer is too thin, the surface hardness becomes low, and when it is too thick, the impact resistance decreases. The thickness of the high-hardness resin layer is preferably 10 to 250 μm, more preferably 30 to 200 μm, and particularly preferably 60 to 150 μm.

[0217] 3. Lamination of base material layer and high hardness resin layer

[0218] As described above, there may be other layers between the substrate layer and the high hardness resin layer. Here, the case of laminating the high hardness resin layer on the substrate layer is described. The lamination method is not particularly limited, and lamination can be performed in the same manner when other layers are present. For example, there are: a method of overlapping the substrate layer and the high hardness resin layer formed separately, and then heating and pressing the two; a method of overlapping the substrate layer and the high hardness resin layer formed separately, and then bonding the two with an adhesive; a method of co-extruding the substrate layer and the high hardness resin layer; a method of in-mold molding the substrate layer and integrating it with the pre-formed high hardness resin layer, and other various methods. Among these, from the perspective of manufacturing cost and productivity, the co-extrusion molding method is preferred.

[0219] The method of co-extrusion is not particularly limited. For example, in the feed block method, a high hardness resin layer is arranged on one surface of the substrate layer using a feed block, and after being extruded into a sheet using a T-die, it is passed through a molding roller while being cooled, thereby forming a desired laminate. In addition, in the multi-manifold method, a high hardness resin layer is arranged on one surface of the substrate layer in a multi-manifold die, and after being extruded into a sheet, it is passed through a molding roller while being cooled, thereby forming a desired laminate. At this time, the rotation speed (m / min) ratio of the molding roller and the sheet pulling roller is controlled, and the sheet is stretched in a uniaxial direction while being cooled. The stretching ratio is controlled to be 1.0 to 1.5 times to control the in-plane delay of the resin sheet. The in-plane delay of the resin sheet of the present invention when measured at a wavelength of 543nm is 4000nm or more, preferably 4500 to 10000nm, and more preferably 5500 to 8000nm. The in-plane retardation of the resin sheet is 4000 nm or more, and after the resin sheet is bonded as a front panel of a liquid crystal panel, even if the liquid crystal display screen is viewed wearing polarized sunglasses, coloring or color unevenness is less likely to occur, which is preferred.

[0220] The total thickness of the substrate layer and the high hardness resin layer is preferably 0.5 to 3.5 mm, more preferably 0.5 to 3.0 mm, and particularly preferably 1.2 to 3.0 mm. By making the total thickness 0.5 mm or more, the rigidity of the sheet can be maintained. In addition, by being 3.5 mm or less, when a touch panel is provided under the sheet, the sensitivity of the touch sensor can be prevented from being deteriorated. The thickness of the substrate layer accounts for a proportion of the total thickness of the substrate layer and the high hardness resin layer, preferably 75% to 99%, more preferably 80% to 99%, and particularly preferably 85% to 99%. By being within the above range, hardness and impact resistance can be combined.

[0221] 4. Hard coating, hard coating anti-glare layer

[0222] The resin sheet of the present invention has a hard coating layer or a hard coating anti-glare layer. Other layers may exist between the hard coating layer, the hard coating anti-glare layer and the high hardness resin layer, and preferably the hard coating layer and the hard coating anti-glare layer are laminated on the high hardness resin layer. The hard coating layer and the hard coating anti-glare layer are preferably made of an acrylic hard coating layer. In this specification, "acrylic hard coating layer" refers to a coating film in which a monomer or oligomer or prepolymer containing a (meth)acryloyl group as a polymerizing group is polymerized to form a cross-linked structure. As a composition of the acrylic hard coating layer, it is preferred to contain 2 to 98% by mass of a (meth)acrylic monomer, 2 to 98% by mass of a (meth)acrylic oligomer and 0 to 15% by mass of a surface modifier, and it is also preferred to contain 0.001 to 7 parts by mass of a photopolymerization initiator relative to 100 parts by mass of the total of the (meth)acrylic monomer, the (meth)acrylic oligomer and the surface modifier.

[0223] The hard coat layer and the hard coat antiglare layer more preferably contain 5 to 50% by mass of a (meth)acrylic monomer, 50 to 94% by mass of a (meth)acrylic oligomer and 1 to 10% by mass of a surface modifier, and particularly preferably contain 20 to 40% by mass of a (meth)acrylic monomer, 60 to 78% by mass of a (meth)acrylic oligomer and 2 to 5% by mass of a surface modifier.

[0224] The amount of the photopolymerization initiator is more preferably 0.01 to 5 parts by mass, particularly preferably 0.1 to 3 parts by mass, based on 100 parts by mass of the total of the (meth)acrylic monomer, the (meth)acrylic oligomer, and the surface modifier.

[0225] (1) (Meth) acrylic acid monomer

[0226] As the (meth)acrylic monomer, any monomer having a (meth)acryloyl group as a functional group in the molecule can be used, and the monomer may be a monofunctional monomer, a difunctional monomer, or a trifunctional or higher-functional monomer.

[0227] Examples of the monofunctional monomer include (meth)acrylic acid and (meth)acrylic acid esters. Specific examples of the difunctional and / or trifunctional or higher (meth)acrylic acid monomers include diethylene glycol di(meth)acrylate, dipropylene glycol di(meth)acrylate, tripropylene glycol di(meth)acrylate, 1,6-hexanediol di(meth)acrylate, bisphenol A diglycidyl ether di(meth)acrylate, tetraethylene glycol di(meth)acrylate, hydroxypivalic acid neopentyl glycol diacrylate, neopentyl glycol di(meth)acrylate, 1,4-butylene glycol diacrylate, and 1,3-butylene glycol di(meth)acrylate. Butanediol, dicyclopentanyl di(meth)acrylate, polyethylene glycol diacrylate, 1,4-butylene glycol oligomer acrylate, neopentyl glycol oligomer acrylate, 1,6-hexanediol oligomer acrylate, trimethylolpropane tri(meth)acrylate, trimethylolpropane ethoxy tri(meth)acrylate, trimethylolpropane propoxy tri(meth)acrylate, pentaerythritol tri(meth)acrylate, glyceryl propoxy tri(meth)acrylate, trimethylolpropane trimethacrylate, trimethylolpropane ethylene oxide adduct triacrylate, glycerol propylene oxide adduct triacrylate, pentaerythritol tetraacrylate, etc.

[0228] The hard coat antiglare layer may contain one or two or more (meth)acrylic monomers.

[0229] (2) (Meth)acrylic acid oligomer

[0230] As (meth)acrylic oligomers, there can be cited difunctional or higher polyfunctional urethane (meth)acrylate oligomers [hereinafter, also referred to as multifunctional urethane (meth)acrylate oligomers], difunctional or higher polyfunctional polyester (meth)acrylate oligomers [hereinafter, also referred to as multifunctional polyester (meth)acrylate oligomers], difunctional or higher polyfunctional epoxy (meth)acrylate oligomers [hereinafter, also referred to as multifunctional epoxy (meth)acrylate oligomers], etc. The hard coat antiglare layer may contain one or more (meth)acrylic oligomers.

[0231] Examples of the multifunctional polyurethane (meth)acrylate oligomer include: an amine reaction product of a (meth)acrylate monomer having at least one (meth)acryloyloxy group and a hydroxyl group in one molecule and a polyisocyanate; an amine reaction product of an isocyanate compound obtained by reacting a polyol with a polyisocyanate and a (meth)acrylate monomer having at least one (meth)acryloyloxy group and a hydroxyl group in one molecule; and the like.

[0232] Examples of the (meth)acrylate monomer having at least one (meth)acryloyloxy group and a hydroxyl group in one molecule used for the amination reaction include 2-hydroxyethyl (meth)acrylate, 2-hydroxypropyl (meth)acrylate, 2-hydroxybutyl (meth)acrylate, 2-hydroxy-3-phenoxypropyl (meth)acrylate, glycerol di(meth)acrylate, trimethylolpropane di(meth)acrylate, pentaerythritol tri(meth)acrylate, and dipentaerythritol penta(meth)acrylate.

[0233] Examples of the polyisocyanate used for the amination reaction include hexamethylene diisocyanate, lysine diisocyanate, isophorone diisocyanate, dicyclohexylmethane diisocyanate, toluene diisocyanate, xylylene diisocyanate, diisocyanates obtained by hydrogenating aromatic isocyanates among these diisocyanates (for example, diisocyanates such as hydrogenated toluene diisocyanate and hydrogenated xylylene diisocyanate), di- or tri-polyisocyanates such as triphenylmethane triisocyanate and dimethylene triphenyl triisocyanate, and polyisocyanates obtained by polymerizing diisocyanates.

[0234] As polyols used for urethanization reaction, generally, in addition to aromatic, aliphatic and alicyclic polyols, polyester polyols, polyether polyols, etc. can also be used. Generally, as aliphatic and alicyclic polyols, 1,4-butanediol, 1,6-hexanediol, neopentyl glycol, ethylene glycol, propylene glycol, trimethylolethane, trimethylolpropane, dimethylolheptane, dimethylolpropionic acid, dimethylolbutyric acid, glycerin, hydrogenated bisphenol A, etc. can be mentioned.

[0235] As polyester polyol, compounds obtained by dehydration condensation reaction of the above-mentioned polyols and polycarboxylic acids can be cited. As specific compounds of polycarboxylic acids, succinic acid, adipic acid, maleic acid, trimellitic acid, hexahydrophthalic acid, phthalic acid, isophthalic acid, terephthalic acid, etc. can be cited. These polycarboxylic acids can also be acid anhydrides. In addition, as polyether polyol, in addition to polyalkylene glycol, polyoxyalkylene modified polyols obtained by reaction of the above-mentioned polyols or phenols with alkylene oxides can also be cited.

[0236] In addition, the multifunctional polyester (meth) acrylate oligomer can be obtained by a dehydration condensation reaction using (meth) acrylic acid, a polycarboxylic acid and a polyol. As the polycarboxylic acid used for the dehydration condensation reaction, succinic acid, adipic acid, maleic acid, itaconic acid, trimellitic acid, pyromellitic acid, hexahydrophthalic acid, phthalic acid, isophthalic acid, terephthalic acid, etc. can be listed. These polycarboxylic acids can also be anhydrides. In addition, as the polyol used for the dehydration condensation reaction, 1,4-butanediol, 1,6-hexanediol, diethylene glycol, triethylene glycol, propylene glycol, neopentyl glycol, dimethylol heptane, dimethylol propionic acid, dimethylol butyric acid, trimethylol propane, di-trimethylol propane, pentaerythritol, dipentaerythritol, etc. can be listed.

[0237] The polyfunctional epoxy (meth)acrylate oligomer can be obtained by the addition reaction of polyglycidyl ether and (meth)acrylic acid. Examples of the polyglycidyl ether include ethylene glycol diglycidyl ether, propylene glycol diglycidyl ether, tripropylene glycol diglycidyl ether, 1,6-hexanediol diglycidyl ether, and bisphenol A diglycidyl ether.

[0238] (3) Surface modifier

[0239] The surface modifier used in the present invention is a substance capable of changing the surface properties of the hard coating anti-glare layer, such as a leveling agent, an antistatic agent, a surfactant, a water-repellent and an oil-repellent, an inorganic particle, an organic particle, etc.

[0240] Examples of the leveling agent include polyether-modified polyalkylsiloxane, polyether-modified siloxane, polyester-modified hydroxyl-containing polyalkylsiloxane, polyether-modified polydimethylsiloxane having an alkyl group, modified polyether, and silicone-modified acrylic.

[0241] Examples of the antistatic agent include glycerin fatty acid ester monoglyceride, glycerin fatty acid ester organic acid monoglyceride, polyglycerin fatty acid ester, sorbitan fatty acid ester, cationic surfactants, and anionic surfactants.

[0242] Examples of the inorganic particles include silica particles, alumina particles, zirconia particles, silicon particles, silver particles, and glass particles.

[0243] Examples of the organic particles include acrylic particles and silicone particles.

[0244] Examples of the surfactant and water- and oil-repellent agent include fluorine-containing surfactants and water- and oil-repellent agents such as oligomers containing a fluorine-containing group and a lipophilic group; and oligomers containing a fluorine-containing group, a hydrophilic group, a lipophilic group, and a UV reactive group.

[0245] (4) Photopolymerization initiator

[0246] The hard coat layer and the hard coat antiglare layer may contain a photopolymerization initiator. In the present specification, the photopolymerization initiator refers to a photo radical generator.

[0247] Examples of the monofunctional photopolymerization initiator that can be used in the present invention include: 4-(2-hydroxyethoxy)phenyl(2-hydroxy-2-propyl)ketone [Darocure 2959: manufactured by Merck]; α-hydroxy-α,α'-dimethylacetophenone [Darocure 1173: manufactured by Merck]; acetophenone-based initiators such as methoxyacetophenone, 2,2'-dimethoxy-2-phenylacetophenone [IRGACURE-651], and 1-hydroxy-cyclohexyl phenyl ketone; benzoin ether-based initiators such as benzoin ethyl ether and benzoin isopropyl ether; and halogenated ketones, acylphosphine oxides, acylphosphonates, and the like.

[0248] (5) Method for forming hard coating layer and hard coating antiglare layer

[0249] The method for forming the hard coat layer and the hard coat antiglare layer is not particularly limited, and they can be formed, for example, by applying a hard coat liquid on a layer (eg, a high hardness resin layer) below the hard coat antiglare layer and then photopolymerizing the layer.

[0250] The method for applying the hard coating liquid (polymerizable composition) is not particularly limited, and a known method can be used, for example, spin coating, dip coating, spray coating, slide coating, rod coating, roll coating, gravure coating, meniscus coating, flexographic printing, screen printing, beat coating, brush coating, etc.

[0251] As the lamp used for light irradiation in photopolymerization, a lamp having a light emission distribution at a wavelength of 420 nm or less can be used, and examples thereof include low-pressure mercury lamps, medium-pressure mercury lamps, high-pressure mercury lamps, ultra-high-pressure mercury lamps, chemical lamps, black light lamps, microwave-excited mercury lamps, metal halide lamps, etc. Among them, high-pressure mercury lamps or metal halide lamps are preferred because they efficiently emit light in the active wavelength region of the initiator, and do not emit a large amount of short-wavelength light that reduces the viscoelastic properties of the obtained polymer due to crosslinking, or long-wavelength light that heats and evaporates the reaction composition.

[0252] The irradiation intensity of the lamp is a factor affecting the polymerization degree of the obtained polymer, and can be appropriately controlled according to the performance of each target product. When a conventional cleavage-type initiator having an acetophenone group is used, the irradiation intensity is preferably 0.1 to 300 mW / cm 2 It is particularly preferred to use a metal halide lamp with an illumination of 10 to 40 mW / cm 2 .

[0253] The photopolymerization reaction is inhibited by oxygen in the air or oxygen dissolved in the reactive composition. Therefore, it is desirable to implement the light irradiation by a method that can eliminate the reaction inhibition caused by oxygen. As one of such methods, there is a method of covering the reactive composition with a film made of polyethylene terephthalate or Teflon to block contact with oxygen, and irradiating the reactive composition with light through the film. Alternatively, the composition may be irradiated with light through a light-transmitting window in an inert atmosphere in which oxygen is replaced with an inert gas such as nitrogen or carbon dioxide.

[0254] When light irradiation is performed under an inert atmosphere, a certain amount of inert gas may be introduced to keep the atmospheric oxygen concentration at a low level. By introducing the inert gas, an airflow is generated on the surface of the reactive composition, causing the monomer to evaporate. In order to suppress the level of monomer evaporation, the airflow velocity of the inert gas is preferably 1 m / sec or less, more preferably 0.1 m / sec or less, measured by the relative velocity of the laminate coated with the hard coating liquid moving under the inert gas atmosphere. By setting the airflow velocity within the above range, the monomer evaporation caused by the airflow can be substantially suppressed.

[0255] For the purpose of improving the adhesion of hard coat layer and hard coat anti-glare layer, the coated surface is sometimes pre-treated. As treatment examples, known methods such as sandblasting, solvent treatment, corona discharge treatment, chromic acid treatment, flame treatment, hot air treatment, ozone treatment, ultraviolet treatment, and the primer treatment using resin composition can be listed.

[0256] The irradiation output using UV light (254nm) is 20mW / cm 2 When irradiated with ultraviolet rays by a metal halide lamp, the pencil hardness of the hard coating layer and the hard coating anti-glare layer is preferably 2H or more.

[0257] As the film thickness of the hard coat layer and the hard coating anti-glare layer, it is desirable to be 1 μm or more and 40 μm or less, and more desirable to be 2 μm or more and 10 μm or less. By having a film thickness of 1 μm or more, sufficient hardness can be obtained. In addition, by having a film thickness of 40 μm or less, cracks can be suppressed during bending. Among them, the film thickness of the hard coating anti-glare layer can be measured by observing the cross section using a microscope, etc., and actually measuring from the coating film interface to the surface.

[0258] The hard coating layer and the hard coating anti-glare layer can be produced by applying an acrylic hard coating layer between a mirror mold or an anti-glare mold and a high-hardness resin, irradiating UV light to cure it, and then demolding it from the mirror mold or the anti-glare mold. When a mirror mold is used, the resin sheet has a mirror hard coating layer; when an anti-glare mold is used, the resin sheet has a hard coating anti-glare layer. The materials of the mirror mold and the anti-glare mold can be any material as long as they can transmit UV light, and the materials include glass, transparent resin, etc.

[0259] The hard coating layer and the hard coating anti-glare layer can be further modified. For example, any one or more of anti-reflection treatment, anti-fouling treatment, anti-static treatment, weathering treatment and anti-glare treatment can be implemented. These treatment methods are not particularly limited, and known methods can be used. For example, a method of applying a reflection reducing coating, a method of evaporating a dielectric film, a method of applying an anti-static coating, etc. can be cited.

[0260] The pencil hardness of the resin sheet of the present invention is preferably 2H or more, for example, 2H to 4H, and particularly preferably 3H to 4H. The pencil hardness of the resin sheet referred to herein refers to the hardness of the hardest pencil that does not produce a scratch when a pencil is pressed at an angle of 45 degrees and a load of 750 g on the surface of the hard-coated antiglare layer, and the hardness of the pencil is gradually increased (based on the pencil scratch hardness test of JIS K 5600-5-4).

[0261] 5. Resin film (X)

[0262] The present invention is a molding resin sheet having a resin film (X) having an in-plane retardation of 50 nm or less when measured at a wavelength of 543 nm bonded to one side surface of the resin sheet using an adhesive layer containing an adhesive. It is preferred to bond a resin film (X) having an in-plane retardation of 45 nm or less, and it is more preferred to bond a resin film (X) having an in-plane retardation of 3 to 45 nm. By bonding a resin film (X) having an in-plane retardation of 50 nm or less, after bonding to the resin sheet, even if the lag axes of the resin film (X) and the resin sheet or the combination of the lag axis and the advance axis are offset due to molding during thermoforming, after bonding the molding resin sheet as a front panel of a liquid crystal panel, even if polarized sunglasses are worn to view the liquid crystal display screen, coloring or color unevenness is not likely to occur, which is preferred.

[0263] A preferred embodiment of the present invention is to laminate a resin film (X) on the side of the substrate layer containing a polycarbonate resin (a1). In addition, another preferred embodiment of the present invention is that the resin film (X) includes a polycarbonate film containing a polycarbonate resin (a1). Further, another preferred embodiment of the present invention is that the resin film (X) includes a film touch sensor obtained by applying a sensor electrode on a substrate film. As the above-mentioned substrate film, COP (cycloolefin polymer), COC (cycloolefin copolymer), acrylic resin, polycarbonate resin, PET resin, etc. can be used, and polycarbonate resin can be preferably used. As the above-mentioned sensor electrode, a resistive film type sensor, an electrostatic capacitance type sensor, etc. configured with a transparent electrode made of ITO, etc. can be listed.

[0264] 6. Adhesive

[0265] The adhesive may be a transparent optical paste, and preferably, as the adhesive layer, Lintec's optically clear adhesive sheet (OCA: Opteria series), Nitto Denko Corporation's optically transparent adhesive sheet LUCIACS series, Sekisui Chemical Co., Ltd.'s highly transparent double-sided tape, Asahi Kasei Corporation's display optical adhesive silicone, etc. are used.

[0266] The haze of the resin sheet of the present invention is preferably 2 to 30%, more preferably 4 to 25%. The haze is a value measured in accordance with JIS K 7136 using HR-100 manufactured by Murakami Color Research Laboratory.

[0267] According to one embodiment of the present invention, a resin molded product obtained by molding using the above-mentioned molding resin sheet can be provided. The molding method is not particularly limited, and according to the characteristics of the resin sheet of the present invention, it is suitable for thermoforming. Thermoforming can be performed using methods commonly used in this field, for example, hot pressing molding, pressure molding, vacuum molding, and TOM molding. The molding temperature is preferably 100°C to 200°C.

[0268] Example

[0269] Hereinafter, although the Example of this invention is illustrated, this invention is not limited to a form of an Example.

[0270] <Measurement of glass transition temperature (Tg) and melting point>

[0271] The glass transition temperatures of the polycarbonate resins and high hardness resins used in the examples and comparative examples and the melting points of the protective films were measured using a differential scanning calorimeter DSC7020 manufactured by Hitachi High-Technologies at a heating rate of 10°C / min in a nitrogen atmosphere. The weight of the resin used for the measurement was 10 to 20 mg.

[0272] <Measurement of pencil hardness of resin sheet>

[0273] The resin sheets produced in the examples and comparative examples were evaluated using a pencil scratch hardness test based on JIS K 5600-5-4. A pencil was pressed against the surface of the hard-coated anti-glare layer at an angle of 45 degrees and a load of 750 g, and the hardness of the pencil was gradually increased. The hardness of the hardest pencil that did not produce scratches was evaluated as the pencil hardness. A hardness of 2H or more was considered acceptable.

[0274] <Production of curved molded products and evaluation of hard coating cracks after molding>

[0275] The resin sheets manufactured in the examples and comparative examples were thermoformed. For Examples 1 to 3, 5 to 15, Comparative Examples 1 to 6, and 8 to 11, a hot press mold with a gap (a gap between the molded sheets above and below the mold) of 2 mm and a molding R of 50 mm was used, and for Example 4 and Comparative Example 7, a hot press mold with a gap of 3.5 mm and a molding R of 100 mm was used. The pressure applied to the hot press mold was 0.6 MPa. The material of the mold was aluminum. During thermoforming, the temperature of the mold was 124°C in Examples 1 to 5, 7 to 11, 13 to 15, Comparative Examples 1 to 4, 9, and 10, and 143°C in Examples 6, 12, and Comparative Examples 5 to 8 and 11.

[0276] The obtained molded product was checked for cracks in the 50 mmR portion or the 100 mmR portion. In addition, when a resin sheet having a total thickness of 0.5 mm, 1.2 mm, or 1.5 mm for the base layer and the high-hardness resin layer was molded using a hot press mold with a gap of 2 mm, a single-layer polycarbonate sheet of 1.5 mm, 0.8 mm, or 0.5 mm was placed underneath, respectively, and hot press molding was performed in such a way that the total thickness was 2 mm.

[0277] <Flow marks>

[0278] The laminated bodies of the high hardness resin layer and the polycarbonate resin layer before forming the hard coating layer produced in the examples and comparative examples were visually inspected under a three-wavelength fluorescent lamp to confirm the presence or absence of scaly patterns and white turbidity. When neither scaly patterns nor white turbidity was observed, it was evaluated as "no flow marks", and when either scaly patterns or white turbidity was observed, it was evaluated as "with flow marks".

[0279] <Measurement of in-plane retardation>

[0280] The retardation of the resin sheet or resin film was measured using the birefringence evaluation device WPA-200-L from Photonic Lattice. The measurement wavelength was 543nm. In the measurement of the retardation domain exceeding 3500nm, since it could not be measured using the attached standard lens, a high phase difference measurement lens K4 FUJINON1: 1.4 / 16mm HF16HA-1B was used.

[0281] <Measurement of Haze of Resin Sheet>

[0282] Evaluation was performed in accordance with JIS K 7136 using HR-100 manufactured by Murakami Color Research Laboratory.

[0283] Example 1: R100 (Tg 124°C) / low TgPC (Tg 125°C) / 1.2mmt

[0284] A multilayer extruder having a single screw extruder with a screw diameter of 35 mm, a single screw extruder with a screw diameter of 65 mm, a feed block connected to each extruder, and a T-die connected to the feed block was used to form a laminate consisting of a substrate layer and a high-hardness resin layer. Specifically, a high-hardness resin (B2) (a copolymer of 21% by mass of methyl methacrylate structural units, 64% by mass of styrene structural units, and 15% by mass of maleic anhydride structural units; RESISFY R100 (manufactured by Denka)) was continuously introduced into a single screw extruder with a screw diameter of 35 mm, and extruded at a barrel temperature of 230°C and a discharge rate of 2.6 kg / h. In addition, a polycarbonate resin (Iupizeta T-1380; manufactured by Mitsubishi Gas Chemical) was continuously introduced into a single screw extruder with a screw diameter of 65 mm, and extruded at a barrel temperature of 240°C and a discharge rate of 50.0 kg / h.

[0285] The extruded high hardness resin and polycarbonate resin are introduced into two kinds of two-layer feed blocks with distribution pins, and the high hardness resin and polycarbonate resin are laminated at a temperature of 240°C. Then, it is introduced into a T-die at a temperature of 240°C and extruded into a sheet. While transferring the mirror surface using three mirror-finished rollers set at temperatures of 120°C, 130°C, and 190°C from the upstream side, it is cooled and stretched to obtain a laminate of a high hardness resin layer and a polycarbonate resin layer (substrate layer). The stretching ratio is 1.3 times. The thickness of the obtained laminate is 1.2 mm, and the thickness of the high hardness resin layer is 60 μm near the center.

[0286] A hard coat antiglare layer is formed on the high hardness resin layer side of the laminate obtained above. The material of the hard coat antiglare layer is as follows.

[0287] Relative to

[0288] U6HA: Hexafunctional urethane acrylate oligomer (manufactured by Shin-Nakamura Chemical Industry Co., Ltd.) 60 mass %,

[0289] 4EG-A: PEG200# diacrylate (manufactured by Kyoeisha Chemical Co., Ltd.) 35% by mass, and

[0290] RS-90: 100 parts by mass of a mixture of 5% by mass of an oligomer containing a fluorine-containing group, a hydrophilic group, a lipophilic group, and a UV-reactive group (manufactured by DIC Corporation),

[0291] Photopolymerization initiator: 1 part by mass of I-184 (manufactured by BASF Corporation [compound name: 1-hydroxy-cyclohexyl phenyl ketone]).

[0292] The above-mentioned material was coated on the laminate using a bar coater, and the concave-convex surface of a 2 mm thick frosted glass plate with a haze of 10% was covered from above, and a metal halide lamp (20 mW / cm 2 ) for 5 seconds to cure the hard coating material, and after the hard coating anti-glare layer is attached, the frosted glass plate is peeled off to prepare a resin sheet. The film thickness of the hard coating anti-glare layer is 6 μm. The haze of the resin sheet is 9%, and the in-plane retardation is 6200 to 6500 nm.

[0293] A polycarbonate film (FS-2000, 100 μmt, manufactured by Mitsubishi Gas Chemical) was bonded to the substrate layer side of the resin sheet using an adhesive (acrylic OCA) to prepare a molding resin sheet. The polycarbonate film had a thickness of 0.1 mm and an in-plane retardation of 20 nm or less.

[0294] Example 2: R100 (Tg 124°C) / low TgPC (Tg 125°C) / 2mmt

[0295] The ejection rate of the polycarbonate resin extruded by a single screw extruder is set to 83.0 kg / h, and the thickness of the laminate of the high hardness resin layer and the polycarbonate resin layer (substrate layer) is set to 2 mm (the thickness of the high hardness resin layer is 60 μm near the center). The stretching ratio is 1.17 times. A hard-coated anti-glare layer is formed in the same manner as in Example 1 to prepare a resin sheet. The in-plane retardation of the resin sheet is 6200 to 6500 nm. The method of bonding the polycarbonate film to the resin sheet is the same as in Example 1 to prepare a resin sheet for molding.

[0296] Example 3: R100 (Tg 124°C) / low TgPC (Tg 125°C) / 0.5mmt

[0297] The ejection speeds of the high hardness resin (B2) and the polycarbonate resin when extruding the single screw extruder are set to 4.8 kg / h and 35.0 kg / h, respectively, and the thickness of the laminate of the high hardness resin layer and the polycarbonate resin layer (substrate layer) is set to 0.5 mm (the thickness of the high hardness resin layer is 60 μm near the center). The stretching ratio is 1.5 times. A hard coating anti-glare layer is formed in the same manner as in Example 1 to prepare a resin sheet. The in-plane retardation is 4100 to 4500 nm. The method of bonding the polycarbonate film to the resin sheet is carried out in the same manner as in Example 1 to prepare a resin sheet for molding.

[0298] Example 4: R100 (Tg 124°C) / low Tg PC (Tg 125°C) / 3.5 mmt

[0299] The ejection speeds of the high hardness resin (B2) and the polycarbonate resin when extruding the single screw extruder are set to 1.3 kg / h and 72.0 kg / h, respectively, and the thickness of the laminate of the high hardness resin layer and the polycarbonate resin layer (substrate layer) is set to 3.5 mm (the thickness of the high hardness resin layer is 60 μm near the center). The stretching ratio is 1.1 times. A hard coating anti-glare layer is formed in the same manner as in Example 1 to prepare a resin sheet. The in-plane retardation is 6800 to 7000 nm. The method of bonding the polycarbonate film to the resin sheet is carried out in the same manner as in Example 1 to prepare a resin sheet for molding.

[0300] Example 5: R310 (Tg 141°C) / low TgPC (Tg 125°C) / 2mmt

[0301] The same multilayer extruder as in Example 1 was used to form a laminate consisting of a substrate layer and a high-hardness resin layer. Specifically, a high-hardness resin (B2) (a copolymer of 6% by mass of methyl methacrylate structural units, 71% by mass of styrene structural units, and 23% by mass of maleic anhydride structural units; RESISFY R310 (manufactured by Denka)) was continuously introduced into a single-screw extruder with a screw diameter of 35 mm, and extruded at a barrel temperature of 240°C and a discharge rate of 2.6 kg / h. In addition, a polycarbonate resin (Iupizeta T-1380; manufactured by Mitsubishi Gas Chemical) was continuously introduced into a single-screw extruder with a screw diameter of 65 mm, and extruded at a barrel temperature of 240°C and a discharge rate of 83.0 kg / h.

[0302] Thereafter, a laminate of a high hardness resin layer and a polycarbonate resin layer (base material layer) was obtained by extrusion using a T die in the same manner as in Example 1. The thickness of the obtained laminate was 2 mm, and the thickness of the high hardness resin layer was 60 μm near the center. The stretching ratio was 1.17 times.

[0303] A hard coat antiglare layer was formed in the same manner as in Example 1. The in-plane retardation of the resin sheet was 6200 to 6500 nm. A polycarbonate film was bonded to the resin sheet in the same manner as in Example 1 to prepare a resin sheet for molding.

[0304] Example 6: R310 (Tg 141°C) / S-1000 (Tg 147°C) / 2mmt

[0305] The same multilayer extruder as in Example 1 was used to form a laminate consisting of a substrate layer and a high-hardness resin layer. Specifically, a high-hardness resin (B2) (a copolymer of 6% by mass of methyl methacrylate structural units, 71% by mass of styrene structural units, and 23% by mass of maleic anhydride structural units; RESISFY R310 (manufactured by Denka)) was continuously introduced into a single-screw extruder having a screw diameter of 35 mm, and extruded at a barrel temperature of 240°C and a discharge rate of 2.6 kg / h. In addition, a polycarbonate resin (Iupilon S-1000; manufactured by Mitsubishi Engineering-Plastics Co., Ltd.) was continuously introduced into a single-screw extruder having a screw diameter of 65 mm, and extruded at a barrel temperature of 280°C and a discharge rate of 83.0 kg / h.

[0306] The extruded high-hardness resin and polycarbonate resin were introduced into two kinds of two-layer feed blocks with distribution pins, and the high-hardness resin and polycarbonate resin were laminated at a temperature of 280°C. Then, it was introduced into a T-die at a temperature of 280°C and extruded into a sheet. While transferring the mirror surface using three mirror-finished rollers set at temperatures of 120°C, 130°C, and 190°C from the upstream side, it was cooled and stretched to obtain a laminate of a high-hardness resin layer and a polycarbonate resin layer (substrate layer). The thickness of the obtained laminate was 2 mm, and the thickness of the high-hardness resin layer was 60 μm near the center. The stretching ratio was 1.17 times.

[0307] A hard coat antiglare layer was formed in the same manner as in Example 1. The in-plane retardation of the resin sheet was 6200 to 6500 nm. A polycarbonate film was bonded to the resin sheet in the same manner as in Example 1 to prepare a resin sheet for molding.

[0308] Example 7: PM120N (Tg 120°C) / low Tg PC (Tg 125°C) / 1.5mmt

[0309] The same multilayer extruder as in Example 1 was used to form a laminate consisting of a substrate layer and a high-hardness resin layer. Specifically, a high-hardness resin (B4) (a copolymer of 7% by mass of styrene structural units, 86% by mass of methyl methacrylate structural units, and 7% by mass of N-phenylmaleimide structural units; DELPET PM120N (manufactured by Asahi Kasei Chemicals)) was continuously introduced into a single-screw extruder with a screw diameter of 35 mm, and extruded at a barrel temperature of 230°C and a discharge rate of 2.6 kg / h. In addition, a polycarbonate resin (Iupizeta T-1380; manufactured by Mitsubishi Gas Chemical) was continuously introduced into a single-screw extruder with a screw diameter of 65 mm, and extruded at a barrel temperature of 240°C and a discharge rate of 62.0 kg / h.

[0310] Thereafter, a laminate of a high hardness resin layer and a polycarbonate resin layer (base material layer) was obtained by extrusion using a T die in the same manner as in Example 1. The thickness of the obtained laminate was 1.5 mm, and the thickness of the high hardness resin layer was 60 μm near the center. The stretching ratio was 1.23 times.

[0311] A hard coat antiglare layer was formed in the same manner as in Example 1. The in-plane retardation of the resin sheet was 6200 to 6500 nm. A polycarbonate film was bonded to the resin sheet in the same manner as in Example 1 to prepare a resin sheet for molding.

[0312] Example 8: R200 (Tg 126°C) / low TgPC (Tg 125°C) / 2mmt

[0313] The same multilayer extruder as in Example 1 was used to form a laminate consisting of a substrate layer and a high-hardness resin layer. Specifically, a high-hardness resin (B2) (a copolymer of 26% by mass of methyl methacrylate structural units, 55% by mass of styrene structural units, and 19% by mass of maleic anhydride structural units; RESISFY R200 (manufactured by Denka)) was continuously introduced into a single-screw extruder with a screw diameter of 35 mm, and extruded at a barrel temperature of 230°C and a discharge rate of 2.6 kg / h. In addition, a polycarbonate resin (Iupizeta T-1380; manufactured by Mitsubishi Gas Chemical) was continuously introduced into a single-screw extruder with a screw diameter of 65 mm, and extruded at a barrel temperature of 240°C and a discharge rate of 83.0 kg / h.

[0314] Thereafter, a laminate of a high hardness resin layer and a polycarbonate resin layer (base material layer) was obtained by extrusion using a T die in the same manner as in Example 1. The thickness of the obtained laminate was 2 mm, and the thickness of the high hardness resin layer was 60 μm near the center. The stretching ratio was 1.17 times.

[0315] The material of the hard coating anti-glare layer is the same as that of Example 1. It is coated on the laminate using a bar coater, and the concave and convex surface of a 2 mm thick frosted glass with a haze of 30% is covered from above. A metal halide lamp (20 mW / cm 2 ) for 5 seconds to cure the hard coating material, and after the hard coating anti-glare layer is attached, the frosted glass plate is peeled off to prepare a resin sheet. The film thickness of the hard coating anti-glare layer is 6 μm. The haze of the resin sheet is 29%, and the in-plane retardation of the resin sheet is 6200 to 6500 nm. The method of attaching a polycarbonate film to the resin sheet is carried out in the same manner as in Example 1 to prepare a resin sheet for molding.

[0316] Example 9: C-PC (KH3410UR) (Tg 118°C) / low Tg PC (Tg 125°C) / 2mmt

[0317] The same multilayer extruder as in Example 1 was used to form a laminate consisting of a substrate layer and a high-hardness resin layer. Specifically, a high-hardness resin (B3) (polycarbonate resin; Iupilon KH3410UR (manufactured by Mitsubishi Engineering-Plastics Co., Ltd.)) was continuously introduced and extruded at a barrel temperature of 270°C and a discharge rate of 2.6 kg / h. In addition, a polycarbonate resin (Iupizeta T-1380; manufactured by Mitsubishi Gas Chemical) was continuously introduced into a single-screw extruder having a screw diameter of 65 mm and extruded at a barrel temperature of 240°C and a discharge rate of 83.0 kg / h.

[0318] Thereafter, a laminate of a high hardness resin layer and a polycarbonate resin layer (base material layer) was obtained by extrusion using a T die in the same manner as in Example 1. The thickness of the obtained laminate was 2 mm, and the thickness of the high hardness resin layer was 60 μm near the center. The stretching ratio was 1.17 times.

[0319] A hard coat antiglare layer was formed in the same manner as in Example 8. The in-plane retardation of the resin sheet was 6200 to 6500 nm. A polycarbonate film was bonded to the resin sheet in the same manner as in Example 1 to prepare a molding resin sheet.

[0320] Example 10: Alloy of R100 and PM120N (Tg 123°C) / Low Tg PC (Tg 125°C) / 1.2 mmt

[0321] 75% by mass of a copolymer having 21% by mass of methyl methacrylate structural units, 64% by mass of styrene structural units and 15% by mass of maleic anhydride structural units (RESISFY R100 (manufactured by Denka)) and 25% by mass of a copolymer having 7% by mass of styrene structural units, 86% by mass of methyl methacrylate structural units and 7% by mass of N-phenylmaleimide structural units (DELPET PM120N; manufactured by Asahi Kasei Chemicals) were introduced into an extruder having a screw diameter of 26 mm (TEM-26SS, L / D≈40; manufactured by Toshiba Machine), and melt-kneaded at 240° C. to obtain a high hardness resin (B4).

[0322] The same multilayer extruder as in Example 1 was used to form a laminate consisting of a substrate layer and a high-hardness resin layer. Specifically, the high-hardness resin (B4) was continuously introduced into a single-screw extruder with a screw diameter of 35 mm, and extruded at a barrel temperature of 230°C and a discharge rate of 2.6 kg / h. In addition, a polycarbonate resin (Iupizeta T-1380; manufactured by Mitsubishi Gas Chemical) was continuously introduced into a single-screw extruder with a screw diameter of 65 mm, and extruded at a barrel temperature of 240°C and a discharge rate of 50.0 kg / h.

[0323] Thereafter, a laminate of a high hardness resin layer and a polycarbonate resin layer (base material layer) was obtained by extrusion using a T die in the same manner as in Example 1. The thickness of the obtained laminate was 1.2 mm, and the thickness of the high hardness resin layer was 60 μm near the center. The stretching ratio was 1.3 times.

[0324] A hard coat antiglare layer was formed in the same manner as in Example 8. The in-plane retardation of the resin sheet was 6200 to 6500 nm.

[0325] A polycarbonate film (FS-2000, 200 μmt manufactured by Mitsubishi Gas Chemical) was bonded to the substrate layer side of the resin sheet using an adhesive (acrylic OCA) to prepare a molding resin sheet. The thickness of the polycarbonate film was 0.2 mm, and the in-plane retardation was 45 nm or less.

[0326] Example 11: R310 (Tg 141°C) / low TgPC (Tg 125°C) / 0.5mmt

[0327] The same multilayer extruder as in Example 1 was used to form a laminate consisting of a substrate layer and a high-hardness resin layer. Specifically, a high-hardness resin (B2) (a copolymer of 6% by mass of methyl methacrylate structural units, 71% by mass of styrene structural units, and 23% by mass of maleic anhydride structural units; RESISFY R310 (manufactured by Denka)) was continuously introduced into a single-screw extruder with a screw diameter of 35 mm, and extruded at a barrel temperature of 230°C and a discharge rate of 8 kg / h. In addition, a polycarbonate resin (Iupizeta T-1380; manufactured by Mitsubishi Gas Chemical) was continuously introduced into a single-screw extruder with a screw diameter of 65 mm, and extruded at a barrel temperature of 240°C and a discharge rate of 35.0 kg / h.

[0328] Thereafter, a laminate of a high hardness resin layer and a polycarbonate resin layer (base material layer) was obtained by extrusion using a T die in the same manner as in Example 1. The thickness of the obtained laminate was 0.5 mm, and the thickness of the high hardness resin layer was 100 μm near the center. The stretching ratio was 1.5 times.

[0329] The material of the hard coating anti-glare layer is the same as that of Example 1. It is coated on the laminate by a bar coater, and the concave and convex surface of a 2 mm thick frosted glass with a haze of 4% is covered from above. A metal halide lamp (20 mW / cm 2 ) for 5 seconds to cure the hard coating material, and after the hard coating anti-glare layer is attached, the frosted glass plate is peeled off to prepare a resin sheet. The film thickness of the hard coating anti-glare layer is 6 μm. The haze of the resin sheet is 2%, and the in-plane retardation is 4100 to 4500 nm.

[0330] The method of bonding the polycarbonate film to the resin sheet was carried out in the same manner as in Example 10 to prepare a molding resin sheet.

[0331] Example 12: FPC0220 (Tg 184°C) / E2000 (147°C) / 1.2mmt

[0332] The same multilayer extruder as in Example 1 was used to form a laminate consisting of a substrate layer and a high-hardness resin layer. Specifically, a high-hardness resin (B5) (a polycarbonate resin containing a structural unit represented by the general formula (8); Iupizeta FPC0220 (manufactured by Mitsubishi Gas Chemical)) was continuously introduced into a single-screw extruder having a screw diameter of 35 mm, and extruded at a barrel temperature of 300°C and a discharge rate of 2.6 kg / h. In addition, a polycarbonate resin (Iupilon E2000; manufactured by Mitsubishi Gas Chemical) was continuously introduced into a single-screw extruder having a screw diameter of 65 mm, and extruded at a barrel temperature of 280°C and a discharge rate of 50.0 kg / h.

[0333] The extruded high-hardness resin and polycarbonate resin are introduced into two kinds of two-layer feed blocks with distribution pins, and the high-hardness resin and polycarbonate resin are laminated at a temperature of 280°C. Then, it is extruded into a sheet using a T-die at a temperature of 280°C, and the mirror surface is transferred using three mirror-finished rollers set at temperatures of 120°C, 130°C, and 190°C from the upstream side while cooling and stretching to obtain a laminate of a high-hardness resin layer and a polycarbonate resin layer (substrate layer). The thickness of the obtained laminate is 1.2 mm, and the thickness of the high-hardness resin layer is 60 μm near the center. The stretching ratio is 1.3 times.

[0334] A hard coat antiglare layer was formed in the same manner as in Example 11. The in-plane retardation of the resin sheet was 6200 to 6500 nm.

[0335] The method of bonding the polycarbonate film to the resin sheet was carried out in the same manner as in Example 10 to prepare a molding resin sheet.

[0336] As in Example 1, the first protective film and the second protective film were bonded together.

[0337] Example 13: MS-H (Tg 115°C) / Low Tg PC (Tg 125°C) / 1.2mmt

[0338] The same multilayer extruder as in Example 1 was used to form a laminate consisting of a substrate layer and a high-hardness resin layer. A high-hardness resin (B1) (a resin in which R1 and R2 in the general formula (1) are both methyl groups, R3 in the general formula (2) is a hydrogen atom, and R4 is a cyclohexyl group; containing 75 mol% of a (meth)acrylate structural unit, 25 mol% of an aliphatic vinyl structural unit, and a weight-average molecular weight of 120,000) was continuously introduced into a single-screw extruder having a screw diameter of 35 mm, and extruded at a barrel temperature of 240°C and a discharge rate of 2.6 kg / h. In addition, a polycarbonate resin (Iupizeta T-1380; manufactured by Mitsubishi Gas Chemical) was continuously introduced into a single-screw extruder having a screw diameter of 65 mm, and extruded at a barrel temperature of 240°C and a discharge rate of 50.0 kg / h.

[0339] Thereafter, a laminate of a high hardness resin layer and a polycarbonate resin layer (base material layer) was obtained by extrusion using a T die in the same manner as in Example 1. The thickness of the obtained laminate was 1.2 mm, and the thickness of the high hardness resin layer was 60 μm near the center. The stretching ratio was 1.3 times.

[0340] In the same manner as in Example 11, a hard coat antiglare layer was formed.

[0341] The in-plane retardation of the resin sheet is 6200 to 6500 nm.

[0342] The method of bonding the polycarbonate film to the resin sheet was carried out in the same manner as in Example 10 to prepare a molding resin sheet.

[0343] Example 14: Alloy of V040 and St-MAH resin (Tg 136°C) / low Tg PC (Tg 125°C) / 1.2 mmt

[0344] A copolymer (XIBOND 160 (manufactured by Polyskop) containing 78% by mass of styrene structural units and 22% by mass of maleic anhydride structural units) and an acrylic resin (ALTUGLAS V040 (manufactured by Arkema) 25% by mass were introduced into an extruder (TEM-26SS, L / D≈40; manufactured by Toshiba Machine) having a screw diameter of 26 mm, and melt-kneaded at 240° C. to obtain a high hardness resin (B6).

[0345] The same multilayer extruder as in Example 1 was used to form a laminate consisting of a substrate layer and a high-hardness resin layer. Specifically, the high-hardness resin (B6) was continuously introduced into a single-screw extruder with a screw diameter of 35 mm, and extruded at a barrel temperature of 230°C and a discharge rate of 2.6 kg / h. In addition, a polycarbonate resin (Iupizeta T-1380; manufactured by Mitsubishi Gas Chemical) was continuously introduced into a single-screw extruder with a screw diameter of 65 mm, and extruded at a barrel temperature of 240°C and a discharge rate of 50.0 kg / h.

[0346] Thereafter, a laminate of a high hardness resin layer and a polycarbonate resin layer (base material layer) was obtained by extrusion using a T die in the same manner as in Example 1. The thickness of the obtained laminate was 1.2 mm, and the thickness of the high hardness resin layer was 60 μm near the center. The stretching ratio was 1.3 times.

[0347] A hard coat antiglare layer was formed in the same manner as in Example 8. The in-plane retardation of the resin sheet was 6200 to 6500 nm.

[0348] A polycarbonate film (FS-2000, 200 μmt manufactured by Mitsubishi Gas Chemical) was bonded as a resin film (X) to the substrate layer side of the resin sheet using an adhesive (acrylic OCA) to prepare a molding resin sheet. The polycarbonate film had a thickness of 0.2 mm and an in-plane retardation of 45 nm or less.

[0349] Example 15: Alloy of V020 and St-MAH resin (Tg 132°C) / low Tg PC (Tg 125°C) / 1.2 mmt

[0350] A copolymer (XIBOND 160 (manufactured by Polyskop) containing 78% by mass of styrene structural units and 22% by mass of maleic anhydride structural units) and 75% by mass of an acrylic resin (ALTUGLAS V020 (manufactured by Arkema) were introduced into an extruder (TEM-26SS, L / D≈40; manufactured by Toshiba Machine) having a screw diameter of 26 mm, and melt-kneaded at 240° C. to obtain a high hardness resin (B6).

[0351] The same multilayer extruder as in Example 1 was used to form a laminate consisting of a substrate layer and a high-hardness resin layer. Specifically, the high-hardness resin (B6) was continuously introduced into a single-screw extruder with a screw diameter of 35 mm, and extruded at a barrel temperature of 230°C and a discharge rate of 2.6 kg / h. In addition, a polycarbonate resin (Iupizeta T-1380; manufactured by Mitsubishi Gas Chemical) was continuously introduced into a single-screw extruder with a screw diameter of 65 mm, and extruded at a barrel temperature of 240°C and a discharge rate of 50.0 kg / h.

[0352] Thereafter, a laminate of a high hardness resin layer and a polycarbonate resin layer (base material layer) was obtained by extrusion using a T die in the same manner as in Example 1. The thickness of the obtained laminate was 1.2 mm, and the thickness of the high hardness resin layer was 60 μm near the center. The stretching ratio was 1.3 times.

[0353] A hard coat antiglare layer was formed in the same manner as in Example 8. The in-plane retardation of the resin sheet was 6200 to 6500 nm.

[0354] A polycarbonate film (FS-2000, 200 μmt manufactured by Mitsubishi Gas Chemical) was bonded to the substrate layer side of the resin sheet using an adhesive (acrylic OCA) to prepare a molding resin sheet. The thickness of the polycarbonate film was 0.2 mm, and the in-plane retardation was 45 nm or less.

[0355] Comparative Example 1: MS-H (Tg 115°C) / Low Tg PC (125°C) / 0.5mmt

[0356] The conditions for extruding the high hardness resin (B1) by a single screw extruder were set to a barrel temperature of 230° C. and an ejection rate of 8.0 kg / h, the ejection rate for extruding the polycarbonate resin by a single screw extruder was set to 35.0 kg / h, and the thickness of the laminate of the high hardness resin layer and the polycarbonate resin layer (base material layer) was set to 0.5 mm (the thickness of the high hardness resin layer was 60 μm near the center). The stretching ratio was 1.5 times.

[0357] A hard coat antiglare layer was formed in the same manner as in Example 1. The in-plane retardation of the resin sheet was 4100 to 4500 nm.

[0358] A polycarbonate film (NF-2000NS, 500 μmt, manufactured by Mitsubishi Gas Chemical) was bonded to the substrate layer side of the resin sheet using an adhesive (acrylic OCA) to prepare a molding resin sheet. The thickness of the polycarbonate film was 0.5 mm, and the in-plane retardation was 300 to 400 nm.

[0359] Comparative Example 2: R100 and PMMA alloy (Tg 115°C) / low Tg PC (Tg 125°C) / 1.2 mmt

[0360] 75% by mass of a copolymer (RESISFY R100; manufactured by Denka) composed of 21% by mass of methyl methacrylate structural units, 64% by mass of styrene structural units and 15% by mass of maleic anhydride structural units, and 25% by mass of an acrylic resin (Parapet HR-1000L (PMMA); manufactured by Kuraray Co., Ltd.) were introduced into an extruder (TEM-26SS, L / D≈40; manufactured by Toshiba Machine) having a screw diameter of 26 mm, and melt-kneaded at 240°C to obtain a high hardness resin (B2).

[0361] The same multilayer extruder as in Example 1 was used to form a laminate consisting of a substrate layer and a high-hardness resin layer. Specifically, the high-hardness resin was continuously introduced into a single-screw extruder with a screw diameter of 35 mm, and extruded at a barrel temperature of 230°C and a discharge rate of 2.6 kg / h. In addition, a polycarbonate resin (Iupizeta T-1380; manufactured by Mitsubishi Gas Chemical) was continuously introduced into a single-screw extruder with a screw diameter of 65 mm, and extruded at a barrel temperature of 240°C and a discharge rate of 50.0 kg / h.

[0362] Thereafter, a laminate of a high hardness resin layer and a polycarbonate resin layer (base material layer) was obtained by extrusion using a T die in the same manner as in Example 1. The thickness of the obtained laminate was 1.2 mm, and the thickness of the high hardness resin layer was 60 μm near the center. The stretching ratio was 1.3 times.

[0363] In the same manner as in Example 1, a hard coat antiglare layer was formed.

[0364] The in-plane retardation of the above-mentioned resin sheet is 6200 to 6500 nm. A polycarbonate film (NF-2000NS, 500 μmt manufactured by Mitsubishi Gas Chemical) as a resin film (X) is bonded to the substrate layer side of the above-mentioned resin sheet using an adhesive (acrylic OCA) to prepare a resin sheet for molding. The thickness of the polycarbonate film is 0.5 mm, and the in-plane retardation is 300 to 400 nm.

[0365] Comparative Example 3: R100 (Tg 124°C) / Low Tg PC (Tg 125°C) / 1.2mmt

[0366] A multilayer extruder having a single screw extruder with a screw diameter of 35 mm, a single screw extruder with a screw diameter of 65 mm, a feed block connected to each extruder, and a T-die connected to the feed block was used to form a laminate consisting of a substrate layer and a high-hardness resin layer. Specifically, a high-hardness resin (B2) (a copolymer of 21% by mass of methyl methacrylate structural units, 64% by mass of styrene structural units, and 15% by mass of maleic anhydride structural units; RESISFY R100 (manufactured by Denka)) was continuously introduced into a single screw extruder with a screw diameter of 35 mm, and extruded at a barrel temperature of 230°C and a discharge rate of 2.6 kg / h. In addition, a polycarbonate resin (Iupizeta T-1380; manufactured by Mitsubishi Gas Chemical) was continuously introduced into a single screw extruder with a screw diameter of 65 mm, and extruded at a barrel temperature of 240°C and a discharge rate of 50.0 kg / h.

[0367] The extruded high-hardness resin and polycarbonate resin are introduced into two kinds of two-layer feed blocks with distribution pins, and the high-hardness resin and polycarbonate resin are laminated at a temperature of 240°C. Then, it is introduced into a T-die at a temperature of 240°C and extruded into a sheet, and the mirror surface is transferred using three mirror-finished rollers set at temperatures of 120°C, 130°C, and 190°C from the upstream side while being cooled and stretched to obtain a laminate of a high-hardness resin layer and a polycarbonate resin layer (substrate layer). The stretching ratio is 1.3 times. The thickness of the obtained laminate is 1.2 mm, and the thickness of the high-hardness resin layer is 60 μm near the center. A hard-coated anti-glare layer is formed in the same manner as in Example 1.

[0368] The in-plane retardation of the above-mentioned resin sheet is 3000 to 3500 nm. A polycarbonate film (FS-2000, 100 μmt manufactured by Mitsubishi Gas Chemical) as a resin film (X) is bonded to the substrate layer side of the above-mentioned resin sheet using an adhesive (acrylic OCA) to prepare a resin sheet for molding. The thickness of the polycarbonate film is 0.1 mm, and the in-plane retardation is less than 20 nm.

[0369] Comparative Example 4

[0370] In the same manner as in Example 1, a laminate of a high-hardness resin layer and a polycarbonate resin layer (base material layer) was obtained.

[0371] A hard coat antiglare layer was formed in the same manner as in Example 1. The in-plane retardation of the above-mentioned resin sheet was 6200 to 6500 nm.

[0372] A polycarbonate film (NF-2000 (H11), 500 μmt manufactured by Mitsubishi Gas Chemical) was bonded to the substrate layer side of the resin sheet using an adhesive (acrylic OCA) to prepare a molding resin sheet. The thickness of the polycarbonate film was 0.5 mm, and the in-plane retardation was 5000 to 6000 nm.

[0373] Comparative Example 5: MS-H (Tg 115°C) / S1000 (Tg 147°C) / 1.2mmt

[0374] The same multilayer extruder as in Example 1 was used to form a laminate consisting of a substrate layer and a high-hardness resin layer. Specifically, a high-hardness resin (B1) (a resin in which R1 and R2 in the general formula (1) are both methyl groups, R3 in the general formula (2) is a hydrogen atom, and R4 is a cyclohexyl group; containing 75 mol% of a (meth)acrylate structural unit, 25 mol% of an aliphatic vinyl structural unit, and a weight-average molecular weight of 120,000) was continuously introduced into a single-screw extruder having a screw diameter of 35 mm, and extruded at a barrel temperature of 240°C and a discharge rate of 2.6 kg / h. In addition, a polycarbonate resin (Iupilon S-1000; manufactured by Mitsubishi Engineering-Plastics Corporation) was continuously introduced into a single-screw extruder having a screw diameter of 65 mm, and extruded at a barrel temperature of 280°C and a discharge rate of 50.0 kg / h.

[0375] The extruded high-hardness resin and polycarbonate resin are introduced into two kinds of two-layer feed blocks with distribution pins, and the high-hardness resin and polycarbonate resin are laminated at a temperature of 270°C. Then, it is extruded into a sheet using a T-die at a temperature of 270°C, and the mirror surface is transferred using three mirror-finished rollers set at temperatures of 120°C, 130°C, and 190°C from the upstream side while cooling to obtain a laminate of a high-hardness resin layer and a polycarbonate resin layer (substrate layer). The stretching ratio is 1.3 times. The thickness of the obtained laminate is 1.2 mm, and the thickness of the high-hardness resin layer is 60 μm near the center.

[0376] A hard coat antiglare layer was formed in the same manner as in Example 1. The in-plane retardation of the above-mentioned resin sheet was 6200 to 6500 nm.

[0377] A polycarbonate film (FS-2000, 200 μmt manufactured by Mitsubishi Gas Chemical) was bonded to the substrate layer side of the resin sheet using an adhesive (acrylic OCA) to prepare a molding resin sheet. The thickness of the polycarbonate film was 0.2 mm, and the in-plane retardation was 45 nm or less.

[0378] Comparative Example 6: MS-H (Tg 115°C) / S1000 (Tg 147°C) / 2mmt

[0379] In Comparative Example 5, the ejection speed when the polycarbonate resin is extruded by a single screw extruder is set to 83.0 kg / h, and the thickness of the laminate of the high hardness resin layer and the polycarbonate resin layer (substrate layer) is set to 2 mm (the thickness of the high hardness resin layer is 60 μm near the center). The stretching ratio is 1.17 times. A hard coating anti-glare layer is formed in the same manner as in Example 1. The in-plane retardation of the above-mentioned resin sheet is 6200 to 6500 nm.

[0380] A polycarbonate film (FS-2000, 200 μmt manufactured by Mitsubishi Gas Chemical) was bonded to the substrate layer side of the resin sheet using an adhesive (acrylic OCA) to prepare a molding resin sheet. The thickness of the polycarbonate film was 0.2 mm, and the in-plane retardation was 45 nm or less.

[0381] Comparative Example 7: MS-H (Tg 115°C) / S1000 (Tg 147°C) / 3.5mmt

[0382] In Comparative Example 5, the ejection rates of the high hardness resin (B1) and the polycarbonate resin when extruded by a single screw extruder were set to 1.3 kg / h and 72.0 kg / h, respectively, and the thickness of the laminate of the high hardness resin layer and the polycarbonate resin layer (base material layer) was set to 3.5 mm (the thickness of the high hardness resin layer was 60 μm near the center). The stretching ratio was 1.1 times.

[0383] A hard coat antiglare layer was formed in the same manner as in Example 1. The in-plane retardation of the above-mentioned resin sheet was 6800 to 7000 nm.

[0384] A polycarbonate film (FS-2000, 200 μmt manufactured by Mitsubishi Gas Chemical) was bonded to the substrate layer side of the resin sheet using an adhesive (acrylic OCA) to prepare a molding resin sheet. The thickness of the polycarbonate film was 0.2 mm, and the in-plane retardation was 45 nm or less.

[0385] Comparative Example 8: MS-H (Tg 115°C) / S1000 (Tg 147°C) / 0.5mmt

[0386] In Comparative Example 5, the ejection rates of the high hardness resin (B1) and the polycarbonate resin when extruded by a single screw extruder were set to 4.8 kg / h and 35.0 kg / h, respectively, and the thickness of the laminate of the high hardness resin layer and the polycarbonate resin layer (base material layer) was set to 0.5 mm (the thickness of the high hardness resin layer was 60 μm near the center). The stretching ratio was 1.5 times.

[0387] A hard coat antiglare layer was formed in the same manner as in Example 1. The in-plane retardation of the above-mentioned resin sheet was 4100 to 4500 nm.

[0388] A polycarbonate film (FS-2000, 200 μmt manufactured by Mitsubishi Gas Chemical) was bonded to the substrate layer side of the resin sheet using an adhesive (acrylic OCA) to prepare a molding resin sheet. The thickness of the polycarbonate film was 0.2 mm, and the in-plane retardation was 45 nm or less.

[0389] Comparative Example 9: PMMA (Tg 105°C) / low Tg PC (Tg 125°C) / 0.8 mmt

[0390] A multilayer extruder having a single screw extruder with a screw diameter of 32 mm, a single screw extruder with a screw diameter of 65 mm, a feed block connected to each extruder, and a T-die connected to the feed block was used to form a laminate consisting of a substrate layer and a high-hardness resin layer. Specifically, a high-hardness resin (acrylic resin; Parapet HR-1000L (PMMA); manufactured by Kuraray Co., Ltd.) was continuously introduced into a single screw extruder with a screw diameter of 32 mm and extruded at a barrel temperature of 250°C and a discharge rate of 2.6 kg / h. In addition, a polycarbonate resin (Iupizeta T-1380; manufactured by Mitsubishi Gas Chemical) was continuously introduced into a single screw extruder with a screw diameter of 65 mm and extruded at a barrel temperature of 240°C and a discharge rate of 32.0 kg / h.

[0391] The extruded high hardness resin and polycarbonate resin are introduced into two kinds of two-layer feed blocks with distribution pins, and the high hardness resin and polycarbonate resin are laminated at a temperature of 240°C. Then, it is introduced into a T-die at a temperature of 240°C and extruded into a sheet, and the mirror surface is transferred by three mirror-finished rollers set at 110°C, 140°C, and 185°C from the upstream side while cooling to obtain a laminate of a high hardness resin layer and a polycarbonate resin layer (substrate layer). The thickness of the obtained laminate is 0.8mm, and the thickness of the high hardness resin layer is 60μm near the center. The stretching ratio is 1.43 times.

[0392] A hard coat antiglare layer was formed in the same manner as in Example 1. The in-plane retardation of the above-mentioned resin sheet was 5800 to 6300 nm.

[0393] A polycarbonate film (FS-2000, 200 μmt manufactured by Mitsubishi Gas Chemical) was bonded to the substrate layer side of the resin sheet using an adhesive (acrylic OCA) to prepare a molding resin sheet. The thickness of the polycarbonate film was 0.2 mm, and the in-plane retardation was 45 nm or less.

[0394] Comparative Example 10: FPC0220 (Tg 184°C) / T1380 (125°C) / 1.2mmt

[0395] The same multilayer extruder as in Example 1 was used to form a laminate consisting of a substrate layer and a high-hardness resin layer. Specifically, a high-hardness resin (B5) (a polycarbonate resin containing a structural unit represented by the general formula (8); Iupizeta FPC0220 (manufactured by Mitsubishi Gas Chemical)) was continuously introduced into a single-screw extruder having a screw diameter of 35 mm, and extruded at a barrel temperature of 300°C and a discharge rate of 2.6 kg / h. In addition, a polycarbonate resin (Iupizeta T1380; manufactured by Mitsubishi Gas Chemical) was continuously introduced into a single-screw extruder having a screw diameter of 65 mm, and extruded at a barrel temperature of 240°C and a discharge rate of 50.0 kg / h.

[0396] The extruded high-hardness resin and polycarbonate resin are introduced into two kinds of two-layer feeds with distribution pins, and the high-hardness resin and polycarbonate resin are laminated at a temperature of 280°C. Then, it is extruded into a sheet using a T-die at a temperature of 280°C, and the mirror surface is transferred using three mirror-finished rollers with temperatures set at 120°C, 130°C, and 190°C from the upstream side, while cooling and stretching to obtain a laminate of a high-hardness resin layer and a polycarbonate resin layer (substrate layer). The stretching ratio is 1.3 times. The thickness of the obtained laminate is 1.2mm, and the thickness of the high-hardness resin layer is 60μm near the center.

[0397] A hard coat antiglare layer was formed in the same manner as in Example 1. The in-plane retardation of the above-mentioned resin sheet was 6200 to 6500 nm.

[0398] A polycarbonate film (FS-2000, 200 μmt manufactured by Mitsubishi Gas Chemical) was bonded to the substrate layer side of the resin sheet using an adhesive (acrylic OCA) to prepare a molding resin sheet. The thickness of the polycarbonate film was 0.2 mm, and the in-plane retardation was 45 nm or less.

[0399] Comparative Example 11: S-1000 (Tg 147°C) alone / 2mmt

[0400] A polycarbonate resin identical to that contained in the substrate layer was used in place of the high hardness resin to form a laminate. As an extrusion device, a multilayer extrusion device identical to that used in Example 1 was used. Specifically, a polycarbonate resin (Iupilon S-1000 (manufactured by Mitsubishi Engineering-Plastics Corporation); pencil hardness 3B) was continuously introduced into a single-screw extruder having a screw diameter of 35 mm, and extruded at a barrel temperature of 280°C and a discharge rate of 2.6 kg / h. In addition, a polycarbonate resin (Iupilon S-1000; manufactured by Mitsubishi Engineering-Plastics Corporation) was continuously introduced into a single-screw extruder having a screw diameter of 65 mm, and extruded at a barrel temperature of 280°C and a discharge rate of 83.0 kg / h.

[0401] The extruded polycarbonate resin was introduced into two kinds of two-layer feed blocks with distribution pins and laminated at a temperature of 280°C. Then, it was introduced into a T-die at a temperature of 280°C and extruded into a sheet, and cooled and stretched while transferring the mirror surface using three mirror-finished rollers set at temperatures of 120°C, 130°C, and 190°C from the upstream side to obtain a laminate of polycarbonate resin. The stretching ratio was 1.17 times. The thickness of the obtained laminate was 2 mm.

[0402] A hard coat antiglare layer was formed in the same manner as in Example 1. The in-plane retardation of the above-mentioned resin sheet was 6200 to 6500 nm.

[0403] A polycarbonate film (FS-2000, 200 μmt manufactured by Mitsubishi Gas Chemical) was bonded as a resin film (X) to the substrate layer side of the resin sheet using an adhesive (acrylic OCA) to prepare a molding resin sheet. The polycarbonate film had a thickness of 0.2 mm and an in-plane retardation of 45 nm or less.

[0404] The resin sheets produced in Examples and Comparative Examples were evaluated for hardness, the presence of cracks after molding, flow marks, mold transfer scratches, and the presence of protective film fusion. The results are shown in Table 1 below.

[0405] [Table 1]

[0406]

[0407]

[0408] It was found that the resin sheet of the present invention was excellent in hardness, had no flow marks, and had no appearance abnormalities such as cracks after thermoforming.

[0409] Several embodiments of the present invention have been described, but these embodiments are only provided as examples and are not intended to limit the scope of the invention. These novel embodiments can be implemented in various other ways, and various omissions, substitutions, and changes can be made without departing from the scope of the invention. These embodiments or their variations are included in the scope or spirit of the invention, and are included in the invention described in the scope of the present invention and its equivalent.

Claims

1. A molding resin sheet, characterized in that: A high-hardness resin layer containing a high-hardness resin is provided on one surface of a substrate layer containing a polycarbonate resin (a1), and a hard coating layer or a hard coating antiglare layer is laminated on the surface of the high-hardness resin layer on the side away from the substrate layer to obtain a resin sheet. The glass transition temperatures of the polycarbonate resin (a1) and the high hardness resin satisfy the following relationship: -10℃≤glass transition temperature of high hardness resin -glass transition temperature of polycarbonate resin (a1)≤40℃, The in-plane retardation of the resin sheet when measured at a wavelength of 543 nm is 4000 nm or more, The molding resin sheet is obtained by laminating a resin film (X) having an in-plane retardation of 50 nm or less when measured at a wavelength of 543 nm to the other surface of the substrate layer of the resin sheet using an adhesive layer containing an adhesive.

2. The molding resin sheet according to claim 1, wherein: The polycarbonate resin (a1) is an aromatic polycarbonate resin.

3. The molding resin sheet according to claim 2, wherein: The aromatic polycarbonate resin comprises a structural unit represented by the following general formula 4a:

4. The molding resin sheet according to any one of claims 1 to 3, wherein: The content of the polycarbonate resin (a1) is 75 to 100% by mass based on the total mass of the substrate layer.

5. The molding resin sheet according to any one of claims 1 to 3, wherein: The high hardness resin is selected from the following resins B1 to B6: Resin B1: a copolymer comprising a (meth)acrylate structural unit a represented by the following general formula 1 and an aliphatic vinyl structural unit b represented by the following general formula 2, or an alloy of the copolymer and resin B2, In Formula 1, R1 is a hydrogen atom or a methyl group; R2 is an alkyl group having 1 to 18 carbon atoms, In Formula 2, R3 is a hydrogen atom or a methyl group; R4 is a cyclohexyl group which may be substituted by a hydrocarbon group having 1 to 4 carbon atoms; Resin B2: a copolymer D comprising 6 to 77% by mass of a (meth)acrylate structural unit, 15 to 71% by mass of a styrene structural unit, and 8 to 23% by mass of an unsaturated dicarboxylic acid structural unit, an alloy of the copolymer D, an alloy of the copolymer D and another high-hardness resin, or an alloy of the copolymer D and an acrylic resin; Resin B3: a copolymer comprising a structural unit c represented by the following general formula 6 and optionally a structural unit d represented by the following general formula 7; Resin B4: a copolymer G comprising 5 to 20% by mass of a styrene structural unit, 60 to 90% by mass of a (meth)acrylate structural unit, and 5 to 20% by mass of an N-substituted maleimide structural unit, or an alloy of the copolymer G and the resin B2; Resin B5: a resin comprising a structural unit e represented by the following general formula 8; Resin B6: An alloy of a copolymer containing 50 to 95% by mass of a styrene structural unit and 5 to 50% by mass of an unsaturated dicarboxylic acid unit, and an acrylic resin.

6. The molding resin sheet according to any one of claims 1 to 3, wherein: The content of the high hardness resin is 70 to 100% by mass based on the total mass of the high hardness resin layer.

7. The molding resin sheet according to any one of claims 1 to 3, wherein: The total thickness of the base material layer and the high-hardness resin layer is 0.5 mm to 3.5 mm.

8. The molding resin sheet according to any one of claims 1 to 3, wherein: The thickness of the base material layer accounts for 75% to 99% of the total thickness of the base material layer and the high-hardness resin layer.

9. The molding resin sheet according to any one of claims 1 to 3, wherein: The molding resin sheet has a haze of 2 to 30%.

10. The molding resin sheet according to any one of claims 1 to 3, wherein: The pencil hardness of the surface of the hard coating layer of the molding resin sheet is 2H or more.

11. The molding resin sheet according to any one of claims 1 to 3, wherein: The resin film (X) in the molding resin sheet includes a polycarbonate film containing a polycarbonate resin (a1).

12. The molding resin sheet according to any one of claims 1 to 3, wherein: The resin film (X) in the molding resin sheet includes a film touch sensor in which a sensor electrode is applied to a polycarbonate film.

13. The molding resin sheet according to any one of claims 1 to 3, wherein: The adhesive layer of the molding resin sheet is an optical adhesive sheet. 14 . A resin molded product obtained by molding using the molding resin sheet according to claim 1 .